Oriented polyethylene film and articles comprising the same
By adjusting the ratio of polyethylene fraction and nucleating agent, a biaxially oriented and uniaxially oriented multi-layer polyethylene film was prepared, which solved the problem of difficulty in recycling polyethylene film in flexible packaging and improved the mechanical properties of the film. Recyclability, achieving higher processing capacity and optical performance.
Patent Information
- Application Number
- CN202180038144.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-29
- Filing Date
- 2021-03-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2041-03-25
AI Technical Summary
The existing flexible packaging film is composed of a variety of polymer materials, which makes recycling difficult, and the molecular and microstructure of polyethylene is difficult to achieve biaxial orientation, affecting its performance and processability.
A polyethylene-based composition was developed to prepare biaxially oriented and uniaxially oriented multilayer polyethylene films by adjusting the ratio of polyethylene fractions and nucleating agents, expanding the operating window and improving the stiffness and conversion rate of the film. , printability and optical properties, and achieve processability on a larger scale.
The orientation of higher density polyethylene is achieved, the mechanical properties and recyclability of the film are improved, the processing capacity on the tenter frame is enhanced, and the optical and barrier properties are improved.
Smart Images

Figure BDA0003963168810000241 
Figure BDA0003963168810000242 
Figure BDA0003963168810000251
Abstract
Description
Technical Field
[0001] The present invention relates to oriented multilayer polyethylene films, laminates comprising such films, and articles comprising such films and laminates. Background Art
[0002] Along with the global concern about reducing packaging waste and making flexible packaging more sustainable, people are working hard to develop materials and technologies that will enhance the sustainability of flexible packaging.Flexible packaging film structures are usually formed by various types of polymer materials, and the polymer materials include for example polyethylene, polypropylene, ethylene vinyl alcohol, polyethylene terephthalate, polyamide etc.These materials are usually combined to realize the property balance of the scope that exceeds the single material type.However, due to the difference of these materials, final packaging is usually not easy to recycle.Therefore, also move towards single component structure (for example, full polyethylene structure), to improve the recyclability overview.For example, in the case of full polyethylene structure, it will be necessary to strengthen some performance indexes (for example, mechanical properties), to maintain the expected performance level of these structures when formed by different polymer materials, improve recyclability simultaneously.Therefore, new resins and processing technology will be needed to make up the performance defects of polyethylene relative to other material types.
[0003] A relatively new material technology in terms of processing is biaxially oriented polyethylene (BOPE) film. This BOPE film is formed by cast extrusion and then oriented in the machine direction (MD) and then in the transverse direction (TD) in a tenter frame. Alternatively, this process can also be performed simultaneously. Due to the molecular structure, microstructure and crystallization dynamics of polyethylene, it is generally difficult to biaxially orient conventional polyethylene.
[0004] It would be desirable to have new polyethylene-based compositions with good processability for biaxially oriented polyethylene films, and new biaxially oriented polyethylene films with desirable and / or improved properties. It would also be desirable to have new polyethylene-based compositions with good processability for uniaxially oriented (e.g., longitudinal direction oriented) polyethylene films, and new uniaxially oriented polyethylene films with desirable and / or improved properties. Summary of the invention
[0005] The present invention provides compositions based on polyethylene suitable for processing into biaxially oriented multilayer polyethylene films and biaxially oriented multilayer polyethylene films with desired and / or improved properties. In some embodiments, such compositions based on polyethylene can advantageously expand the operating window for stretching films to provide biaxially oriented polyethylene films. For example, by expanding the operating window for biaxial orientation, higher density polyethylene can be oriented, which can improve the rigidity of the film. Other advantages may include, but are not limited to, better conversion rate and printability of the film, improved optics (e.g., higher clarity and lower haze), improved barrier properties of metallized biaxially oriented polyethylene films, and improved processability on larger, wider tenter frames. The present invention also provides compositions based on polyethylene suitable for processing into uniaxially oriented (e.g., longitudinally oriented) multilayer polyethylene films and uniaxially oriented multilayer polyethylene films with desired and / or improved properties.
[0006] In one aspect, a biaxially oriented multilayer polyethylene film comprises at least one layer, the at least one layer comprising:
[0007] (1) A polyethylene-based composition, comprising:
[0008] (a) at least 97 wt. %, based on the total weight of the polyethylene-based composition, of a polyethylene composition comprising:
[0009] (i) 25% to 37% by weight of the density is 0.935 g / cm 3 Up to 0.947g / cm 3 In the range of melt index (I 2 ) a first polyethylene fraction of less than 0.1 g / 10 minutes; and
[0010] (ii) 63 to 75 weight percent of a second polyethylene fraction;
[0011] When using 13 The polyethylene composition has less than 0.10 branches per 1,000 carbon atoms when measured by C NMR, wherein the density of the polyethylene-based composition is at least 0.965 g / cm 3 , and wherein the melt index (I 2 ) is 0.5 g / 10 min to 10 g / 10 min.
[0012] In some embodiments, the polyethylene-based composition comprises at least 99 wt % of the polyethylene composition and is substantially free of any nucleating agent, based on the total weight of the polyethylene-based composition. In some embodiments, the polyethylene-based composition comprises 0 to 19 ppm of total nucleating agent. In some embodiments, the polyethylene-based composition does not contain a nucleating agent.
[0013] In some embodiments, the polyethylene-based composition further comprises 20 ppm to 5000 ppm of a nucleating agent, based on the total weight of the polyethylene-based composition, wherein the nucleating agent comprises 1,2-cyclohexanedicarboxylic acid calcium salt or sodium 4-[(4-chlorobenzoyl)amino]benzoate.
[0014] In another aspect, the invention relates to an article, such as food packaging. In one aspect, an article comprises any of the biaxially oriented multilayer polyethylene films disclosed herein.
[0015] In another aspect, the present invention relates to laminates and articles formed from such laminates. In some embodiments, the laminate comprises: a first film comprising a polyethylene-based sealant film, polyethylene terephthalate, polypropylene, or polyamide; and an oriented multilayer polyethylene film according to any embodiment disclosed herein, wherein the first film is laminated to the multilayer polyethylene film. In one aspect, an article comprises any of the laminates disclosed herein.
[0016] These and other embodiments are described in more detail in the detailed description. DETAILED DESCRIPTION
[0017] Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are by weight, all temperatures are in °C, and all test methods are current as of the filing date of this disclosure.
[0018]
[0046] The term "composition" as used herein refers to a mixture of materials that comprise the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0019] "Polymer" means a polymeric compound prepared by polymerizing monomers, whether of the same or different types. Thus, the generic term polymer embraces the term homopolymer, as defined below, and the term interpolymer, as defined below. Trace amounts of impurities (e.g., catalyst residues) may be incorporated into and / or within the polymer. The polymer may be a single polymer, a polymer blend, or a polymer mixture, including a mixture of polymers formed in situ during polymerization.
[0020] As used herein, the term "homopolymer" refers to a polymer prepared from only one type of monomer, with the understanding that trace amounts of impurities may also be incorporated into the polymer structure.
[0021] As used herein, the term "interpolymer" refers to polymers prepared by polymerizing at least two different types of monomers. Thus, the generic term interpolymer includes copolymers (used to refer to polymers prepared from two different types of monomers) and polymers prepared from more than two different types of monomers.
[0022] As used herein, the term "olefinic polymer" or "polyolefin" refers to a polymer that includes, in polymerized form, a major amount of an olefin monomer, such as ethylene or propylene (by weight of the polymer), and optionally may include one or more comonomers.
[0023] As used herein, the term "ethylene / α-olefin interpolymer" refers to an interpolymer comprising, in polymerized form, a majority amount (>50 mol%) of units derived from ethylene monomer and the remainder of units derived from one or more α-olefins. Typical α-olefins used to form ethylene / α-olefin interpolymers are C 3 -C 10 Olefins.
[0024] As used herein, the term "ethylene / α-olefin copolymer" refers to a copolymer comprising, in polymerized form, a majority amount (>50 mol%) of ethylene monomer and an α-olefin as the only two monomer types.
[0025] As used herein, the term "α-olefin" refers to an olefin having a double bond at the primary or α (alpha) position.
[0026] "Polyethylene" or "ethylene-based polymer" shall mean a polymer comprising a majority amount (>50 mol%) of units derived from ethylene monomers. This includes polyethylene homopolymers or copolymers (meaning units derived from two or more comonomers). Common forms of polyethylene known in the art include low density polyethylene (LDPE); linear low density polyethylene (LLDPE); ultra low density polyethylene (ULDPE); very low density polyethylene (VLDPE); single site catalyzed linear low density polyethylene, including linear and substantially linear low density resins (m-LLDPE); ethylene-based plastomers (POPs) and ethylene-based elastomers (POEs); medium density polyethylene (MDPE); and high density polyethylene (HDPE). These polyethylene materials are generally known in the art; however, the following description may be helpful in understanding the differences between some of these different polyethylene resins.
[0027] The term "LDPE" may also be referred to as "high pressure ethylene polymer" or "highly branched polyethylene" and is defined to mean that the polymer is partially or completely homopolymerized or copolymerized in an autoclave or tubular reactor at a pressure above 14,500 psi (100 MPa) using a free radical initiator such as a peroxide (see, e.g., US 4,599,392, which is hereby incorporated by reference). The density of LDPE resins is typically 0.916 g / cm 3 Up to 0.935g / cm 3 within the range.
[0028] The term "LLDPE" includes those produced using conventional Ziegler-Natta catalyst systems. catalyst system) and a chromium-based catalyst system and a single-site catalyst (including but not limited to substituted mono- or dicyclopentadienyl catalysts (commonly referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts, and polyvalent aryloxyether catalysts (commonly referred to as bisphenylphenoxy), and comprises linear, substantially linear or heterogeneous polyethylene copolymers or homopolymers. LLDPE includes less long chain branching than LDPE and comprises substantially linear ethylene polymers, which are further defined in U.S. Pat. No. 5,272,236, U.S. Pat. No. 5,278,272, U.S. Pat. No. 5,582,923 and U.S. Pat. No. 5,733,155; homogeneously branched linear ethylene polymer compositions, such as those in U.S. Pat. No. 3,645,992; heterogeneously branched ethylene polymers, such as those prepared according to the process disclosed in U.S. Pat. No. 4,076,698; and / or blends thereof (such as U.S. Pat. No. 3,914,342 or U.S. Pat. No. 5,733,155). 5,854,045). LLDPE can be made by gas phase, solution phase or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.
[0029] The term "MDPE" refers to a polyethylene having a density of 0.926 g / cm 3 Up to 0.935g / cm 3 "MDPE" is typically produced using chromium or Ziegler-Natta catalysts or using single-site catalysts, including but not limited to substituted mono- or bis-cyclopentadienyl catalysts (commonly referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts, and polyvalent catalysts aryloxyether catalysts (commonly referred to as bisphenylphenoxy), and typically has a molecular weight distribution ("MWD") greater than 2.5.
[0030] The term "HDPE" refers to a polyethylene having a density greater than about 0.935 g / cm 3 and at most about 0.980 g / cm 3The polyethylene is generally prepared using Ziegler-Natta catalysts, chromium catalysts or single-site catalysts (including but not limited to substituted mono- or bis-cyclopentadienyl catalysts (commonly known as metallocenes), constrained geometry catalysts, phosphinimine catalysts and polyvalent catalysts aryloxyether catalysts (commonly known as bisphenylphenoxy).
[0031] The term "ULDPE" refers to a polyethylene with a density of 0.855 g / cm 3 Up to 0.912g / cm 3 ULDPE is a polyethylene generally prepared with a Ziegler-Natta catalyst, a chromium catalyst or a single-site catalyst (including but not limited to substituted mono- or di-cyclopentadienyl catalysts (commonly referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts and multivalent catalysts (commonly referred to as bisphenylphenoxy). ULDPE includes but is not limited to polyethylene (based on ethylene) plastomers and polyethylene (based on ethylene) elastomers. Polyethylene (based on ethylene) elastomers and plastomers generally have a molecular weight of 0.855 g / cm 3 Up to 0.912g / cm 3 density.
[0032] "Blend", "polymer blend" and the like terms mean a composition of two or more polymers. Such blends may or may not be miscible. Such blends may or may not be phase separated. Such blends may or may not contain one or more domain configurations as determined by transmission electron spectroscopy, light scattering, x-ray scattering, and any other method known in the art. A blend is not a laminate, but one or more layers of a laminate may contain a blend. Such blends may be prepared as dry blends, formed in situ (e.g., in a reactor), melt blends, or using other techniques known to those skilled in the art.
[0033] The terms "comprising," "including," "having," and derivatives thereof are not intended to exclude the presence of any additional components, steps, or procedures, whether or not specifically disclosed. For the avoidance of any doubt, all compositions claimed through use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless stated to the contrary. In contrast, the term "consisting essentially of excludes from the scope of any subsequently recited component, step, or procedure, except those that are not essential to operability. The term "consisting of excludes any ingredient, step, or procedure not specifically recited or listed.
[0034] The present invention generally relates to oriented multilayer polyethylene films. In some embodiments, such films are biaxially oriented. In some embodiments, such films are biaxially oriented using a tenter frame. In some embodiments, such films are uniaxially oriented in the longitudinal direction. Oriented multilayer polyethylene films utilize a polyethylene-based composition in at least one layer, and the polyethylene-based composition can advantageously expand the operating window for stretching films. For example, by expanding the operating window for biaxial orientation, higher density polyethylene can be oriented, which can improve the rigidity of the film. In some embodiments, oriented multilayer polyethylene films can be used for packaging applications.
[0035] In one aspect, a biaxially oriented multilayer polyethylene film comprises at least one layer, the at least one layer comprising:
[0036] (1) A polyethylene-based composition, comprising:
[0037] (a) at least 97 wt. %, based on the total weight of the polyethylene-based composition, of a polyethylene composition comprising:
[0038] (i) 25% to 37% by weight of the density is 0.935 g / cm 3 Up to 0.947g / cm 3 In the range of melt index (I 2 ) a first polyethylene fraction of less than 0.1 g / 10 minutes; and
[0039] (ii) 63 to 75 weight percent of a second polyethylene fraction;
[0040] When using 13 The polyethylene composition has less than 0.10 branches per 1,000 carbon atoms when measured by C NMR, wherein the density of the polyethylene-based composition is at least 0.965 g / cm 3 , and wherein the melt index (I 2 ) is 0.5 g / 10 min to 10 g / 10 min. In some embodiments, the polyethylene-based composition consists of 100 wt % of the polyethylene composition. In some embodiments, the polyethylene-based composition consists essentially of at least 99 wt % of the polyethylene composition.
[0041] In some embodiments, the polyethylene-based composition comprises at least 99 weight percent of the polyethylene composition, based on the total weight of the polyethylene-based composition, and is substantially free of any nucleating agent.
[0042] In some embodiments, the composition based on polyethylene is substantially free of any nucleating agent. The amount of the nucleating agent present in the composition based on polyethylene can be detected by elemental analysis using X-ray fluorescence (XRF) using techniques known to those of ordinary skill in the art. As used herein, in embodiments in which the composition based on polyethylene is substantially free of any nucleating agent, the composition based on polyethylene includes 0 to less than 19ppm of total nucleating agent. In some embodiments, the composition based on polyethylene does not contain any nucleating agent. In some embodiments, the composition based on polyethylene includes 0 to less than 19ppm of 1,2-cyclohexanedicarboxylic acid calcium salt or 4-[(4-chlorobenzoyl)amino] sodium benzoate. In some embodiments, the composition based on polyethylene does not contain any 1,2-cyclohexanedicarboxylic acid calcium salt or 4-[(4-chlorobenzoyl)amino] sodium benzoate.
[0043] It has been found that the absence or substantial absence of nucleating agents in polyethylene-based compositions provides beneficial results after film orientation. However, in some embodiments, one or more nucleating agents may be provided in polyethylene-based compositions. In some embodiments, the polyethylene-based composition comprises 20 ppm to 2000 ppm of nucleating agent, based on the total weight of the polyethylene-based composition.
[0044] In one aspect, a biaxially oriented multilayer polyethylene film comprises at least one layer, the at least one layer comprising:
[0045] (1) A polyethylene-based composition, comprising:
[0046] (a) at least 97 wt. %, based on the total weight of the polyethylene-based composition, of a polyethylene composition comprising:
[0047] (i) 25% to 37% by weight of the density is 0.935 g / cm 3 Up to 0.947g / cm 3 In the range of melt index (I 2 ) a first polyethylene fraction of less than 0.1 g / 10 minutes; and
[0048] (ii) 63 wt % to 75 wt % of a second polyethylene fraction; and
[0049] (b) 20 ppm to 5000 ppm of a nucleating agent, based on the total weight of the polyethylene-based composition, wherein the nucleating agent comprises 1,2-cyclohexanedicarboxylic acid calcium salt or sodium 4-[(4-chlorobenzoyl)amino]benzoate;
[0050] When using 13The polyethylene composition has less than 0.10 branches per 1,000 carbon atoms when measured by C NMR, wherein the density of the polyethylene-based composition is at least 0.965 g / cm 3 , and wherein the melt index (I 2 ) is 0.5 g / 10 min to 10 g / 10 min.
[0051] In another aspect, a biaxially oriented multilayer polyethylene film comprises at least one layer, the at least one layer comprising:
[0052] (1) A polyethylene-based composition, comprising:
[0053] (a) at least 97 wt. %, based on the total weight of the polyethylene-based composition, of a polyethylene composition comprising:
[0054] (i) 25% to 37% by weight of the density is 0.935 g / cm 3 Up to 0.947g / cm 3 In the range of melt index (I 2 ) a first polyethylene fraction of less than 0.1 g / 10 minutes; and
[0055] (ii) 63 wt % to 75 wt % of a second polyethylene fraction; and
[0056] (b) 20 ppm to 5000 ppm of a nucleating agent, based on the total weight of the polyethylene-based composition, wherein the nucleating agent comprises sodium 4-[(4-chlorobenzoyl)amino]benzoate;
[0057] When using 13 The polyethylene composition has less than 0.10 branches per 1,000 carbon atoms when measured by C NMR, wherein the density of the polyethylene-based composition is at least 0.965 g / cm 3 , and wherein the melt index (I 2 ) is 0.5 g / 10 min to 10 g / 10 min.
[0058] In another aspect, a biaxially oriented multilayer polyethylene film comprises at least one layer, the at least one layer comprising:
[0059] (1) A polyethylene-based composition, comprising:
[0060] (a) at least 97 wt. %, based on the total weight of the polyethylene-based composition, of a polyethylene composition comprising:
[0061] (i) 25% to 37% by weight of the density is 0.935 g / cm 3 Up to 0.947g / cm 3 In the range of melt index (I 2 ) a first polyethylene fraction of less than 0.1 g / 10 minutes; and
[0062] (ii) 63 wt % to 75 wt % of a second polyethylene fraction; and
[0063] (b) 20 ppm to 5000 ppm of a nucleating agent, based on the total weight of the polyethylene-based composition, wherein the nucleating agent comprises 1,2-cyclohexanedicarboxylic acid calcium salt; wherein when using 13 The polyethylene composition has less than 0.10 branches per 1,000 carbon atoms when measured by C NMR, wherein the density of the polyethylene-based composition is at least 0.965 g / cm 3 , and wherein the melt index (I 2 ) is 0.5 g / 10 min to 10 g / 10 min.
[0064] In some embodiments, the biaxially oriented film according to any embodiment described herein is oriented in the longitudinal direction at a stretch ratio of 2: 1 to 9: 1, and in the transverse direction at a stretch ratio of 2: 1 to 11: 1. In some embodiments, the biaxially oriented film is oriented in the longitudinal direction at a stretch ratio of 2: 1 to 6: 1, and in the transverse direction at a stretch ratio of 2: 1 to 9: 1. In some embodiments, the biaxially oriented film is oriented in the longitudinal direction at a stretch ratio of 4: 1 to 6: 1, and in the transverse direction at a stretch ratio of 6: 1 to 9: 1.
[0065] In some embodiments, the biaxially oriented multilayer polyethylene film further comprises a second polyethylene composition, wherein the second polyethylene composition exhibits at least two local peaks in the comonomer distribution measured by crystallization elution fractionation, excluding the soluble fraction, wherein one of the peaks is between 40°C and 95°C. In some embodiments, the second polyethylene composition exhibits at least two local peaks in the comonomer distribution measured by crystallization elution fractionation, excluding the soluble fraction, wherein one of the peaks is between 40°C and 90°C. In some embodiments, the second polyethylene composition exhibits at least two local peaks in the comonomer distribution measured by crystallization elution fractionation, excluding the soluble fraction, wherein one of the peaks is between 40°C and 87°C. The density of the second polyethylene composition in some embodiments is 0.928 g / cm 3 Up to 0.940g / cm 3 In some embodiments, the layer comprising the polyethylene-based composition further comprises a second polyethylene composition.
[0066] In some embodiments, the overall density of the biaxially oriented multilayer film is 0.931 g / cm 3 Up to 0.975g / cm 3 .
[0067] In some embodiments, the biaxially oriented multilayer film has a thickness of 5 microns to 50 microns.
[0068] In some embodiments, the biaxially oriented multilayer film further comprises a layer comprising polyamide or ethylene vinyl alcohol.
[0069] In some embodiments, the biaxially oriented multilayer film further comprises an outer layer that is a sealant layer.
[0070] In some embodiments, the biaxially oriented multilayer film includes an outer layer that provides a matte surface. In such embodiments, the outer layer that provides a matte surface has a gloss of less than 50% as measured by ASTM D2457 and an angle of 45°. To provide a matte surface, the outer layer may include 20% to 80% by weight of an ethylene-based polymer and 80% to 20% by weight of a propylene-based polymer as described in PCT Publication No. WO2020 / 001191, which is hereby incorporated by reference herein. For example, in some embodiments, the outer layer comprises a blend of a linear low density polyethylene and a polyethylene random copolymer.
[0071] In some embodiments, the biaxially oriented multilayer film further comprises a layer comprising a metal deposited on an outer layer of the film, wherein the metal comprises Al, Zn, Au, Ag, Cu, Ni, Cr, Ge, Se, Ti, Sn, Si, Mg, or oxides thereof.
[0072] In another aspect, the invention relates to an article, such as food packaging. In one aspect, an article comprises any of the inventive biaxially oriented multilayer polyethylene films disclosed herein.
[0073] In another aspect, the invention relates to laminates and articles formed from such laminates. In some embodiments, the laminate comprises: a first film comprising a polyethylene-based sealant film, polyethylene terephthalate, polypropylene, or polyamide; and a biaxially oriented multilayer polyethylene film according to any embodiment disclosed herein, wherein the first film is laminated to the multilayer polyethylene film. In one aspect, an article comprises any of the laminates disclosed herein.
[0074] In another aspect, the present invention relates to a uniaxially oriented multilayer polyethylene film comprising:
[0075] At least one layer, the at least one layer comprising:
[0076] (1) A polyethylene-based composition, comprising:
[0077] (a) at least 97 wt. %, based on the total weight of the polyethylene-based composition, of a polyethylene composition comprising:
[0078] (i) 25% to 37% by weight of the density is 0.935 g / cm 3 Up to 0.947g / cm 3 In the range of melt index (I 2 ) a first polyethylene fraction of less than 0.1 g / 10 minutes; and
[0079] (ii) 63 to 75 weight percent of a second polyethylene fraction;
[0080] When using 13 The polyethylene composition has less than 0.10 branches per 1,000 carbon atoms when measured by C NMR, wherein the density of the polyethylene-based composition is at least 0.965 g / cm 3 , and wherein the melt index (I 2 ) is 0.5 g / 10 min to 10 g / 10 min. In some embodiments, the film is oriented in the longitudinal direction. In some embodiments, the polyethylene-based composition is composed of 100 wt % of the polyethylene composition. In some embodiments, the polyethylene-based composition is substantially composed of at least 99 wt % of the polyethylene composition.
[0081] In some embodiments, the polyethylene-based composition comprises at least 99 weight percent of the polyethylene composition, based on the total weight of the polyethylene-based composition, and is substantially free of any nucleating agent.
[0082] In some embodiments, the polyethylene-based composition is substantially free of any nucleating agent. As used herein, in embodiments in which the polyethylene-based composition is substantially free of any nucleating agent, the polyethylene-based composition comprises 0 to less than 19 ppm of total nucleating agent. In some embodiments, the polyethylene-based composition does not contain any nucleating agent. In some embodiments, the polyethylene-based composition comprises 0 to less than 19 ppm of 1,2-cyclohexanedicarboxylic acid calcium salt or 4-[(4-chlorobenzoyl)amino] sodium benzoate. In some embodiments, the polyethylene-based composition does not contain any 1,2-cyclohexanedicarboxylic acid calcium salt or 4-[(4-chlorobenzoyl)amino] sodium benzoate.
[0083] It has been found that the absence or substantial absence of nucleating agents in polyethylene-based compositions provides beneficial results after film orientation. However, in some embodiments, one or more nucleating agents may be provided in polyethylene-based compositions. In some embodiments, the polyethylene-based composition comprises 20 ppm to 2000 ppm of nucleating agent, based on the total weight of the polyethylene-based composition.
[0084] In another aspect, the present invention relates to a uniaxially oriented multilayer polyethylene film comprising:
[0085] At least one layer, the at least one layer comprising:
[0086] (1) A polyethylene-based composition, comprising:
[0087] (a) at least 97 wt. %, based on the total weight of the polyethylene-based composition, of a polyethylene composition comprising:
[0088] (i) 25% to 37% by weight of the density is 0.935 g / cm 3 Up to 0.947g / cm 3 In the range of melt index (I 2 ) a first polyethylene fraction of less than 0.1 g / 10 minutes; and
[0089] (ii) 63 wt % to 75 wt % of a second polyethylene fraction; and
[0090] (b) 20 ppm to 5000 ppm of a nucleating agent, based on the total weight of the polyethylene-based composition, wherein the nucleating agent comprises 1,2-cyclohexanedicarboxylic acid calcium salt or 4-
[0091] Sodium [(4-chlorobenzoyl)amino]benzoate;
[0092] When using 13 The polyethylene composition has less than 0.10 branches per 1,000 carbon atoms when measured by C NMR, wherein the density of the polyethylene-based composition is at least 0.965 g / cm 3 , and wherein the melt index (I 2 ) is from 0.5 g / 10 min to 10 g / 10 min. In some embodiments, the film is oriented in the machine direction.
[0093] In another aspect, the present invention relates to a uniaxially oriented multilayer polyethylene film comprising:
[0094] At least one layer, the at least one layer comprising:
[0095] (1) A polyethylene-based composition, comprising:
[0096] (a) at least 97 wt. %, based on the total weight of the polyethylene-based composition, of a polyethylene composition comprising:
[0097] (i) 25% to 37% by weight of the density is 0.935 g / cm 3 Up to 0.947g / cm 3 In the range of melt index (I 2 ) a first polyethylene fraction of less than 0.1 g / 10 minutes; and
[0098] (ii) 63 wt % to 75 wt % of a second polyethylene fraction; and
[0099] (b) 20 ppm to 5000 ppm of a nucleating agent, based on the total weight of the polyethylene-based composition, wherein the nucleating agent comprises 1,2-cyclohexanedicarboxylic acid calcium salt; wherein when using 13 The polyethylene composition has less than 0.10 branches per 1,000 carbon atoms when measured by C NMR, wherein the density of the polyethylene-based composition is at least 0.965 g / cm 3 , and wherein the melt index (I 2 ) is from 0.5 g / 10 min to 10 g / 10 min. In some embodiments, the film is oriented in the machine direction.
[0100] In another aspect, the present invention relates to a uniaxially oriented multilayer polyethylene film comprising:
[0101] At least one layer, the at least one layer comprising:
[0102] (1) A polyethylene-based composition, comprising:
[0103] (a) at least 97 wt. %, based on the total weight of the polyethylene-based composition, of a polyethylene composition comprising:
[0104] (i) 25% to 37% by weight of the density is 0.935 g / cm 3 Up to 0.947g / cm 3 In the range of melt index (I 2 ) a first polyethylene fraction of less than 0.1 g / 10 minutes; and
[0105] (ii) 63 wt % to 75 wt % of a second polyethylene fraction; and
[0106] (b) 20 ppm to 5000 ppm of a nucleating agent, based on the total weight of the polyethylene-based composition, wherein the nucleating agent comprises sodium 4-[(4-chlorobenzoyl)amino]benzoate;
[0107] When using 13 The polyethylene composition has less than 0.10 branches per 1,000 carbon atoms when measured by C NMR, wherein the density of the polyethylene-based composition is at least 0.965 g / cm 3 , and wherein the melt index (I 2 ) is 0.5g / 10 minutes to 10g / 10 minutes. In some embodiments, the film is oriented in the longitudinal direction. In some embodiments, the uniaxially oriented film is oriented in the longitudinal direction with a stretch ratio of 4:1 to 20:1. In some embodiments, the uniaxially oriented film is oriented in the longitudinal direction with a stretch ratio of 4:1 to 16:1. In some embodiments, the uniaxially oriented film is oriented in the longitudinal direction with a stretch ratio of 4:1 to 12:1. In some embodiments, the uniaxially oriented film is oriented in the longitudinal direction with a stretch ratio of 4:1 to 10:1. In some embodiments, the uniaxially oriented film is oriented in the longitudinal direction with a stretch ratio of 4:1 to 9:1.
[0108] In some embodiments, the uniaxially oriented multilayer polyethylene film further comprises a second polyethylene composition, wherein the second polyethylene composition exhibits at least two local peaks in the comonomer distribution measured by crystallization elution fractionation, excluding the soluble fraction, wherein one of the peaks is between 40°C and 95°C. In some embodiments, the fraction forming the peak between 40°C and 95°C accounts for up to 50% by weight of the composition as measured by crystallization elution fractionation. In some embodiments, the second polyethylene composition exhibits at least two local peaks in the comonomer distribution measured by crystallization elution fractionation, excluding the soluble fraction, wherein one of the peaks is between 40°C and 90°C. In some embodiments, the second polyethylene composition exhibits at least two local peaks in the comonomer distribution measured by crystallization elution fractionation, excluding the soluble fraction, wherein one of the peaks is between 40°C and 87°C. The density of the second polyethylene composition in some embodiments is 0.928 g / cm 3 Up to 0.940g / cm 3 In some embodiments, the layer comprising the polyethylene-based composition further comprises a second polyethylene composition.
[0109] In some embodiments, the overall density of the uniaxially oriented multilayer film is 0.931 g / cm 3 Up to 0.975g / cm 3 .
[0110] In some embodiments, the uniaxially oriented multilayer film has a thickness of 5 microns to 50 microns.
[0111] In some embodiments, the uniaxially oriented multilayer film further comprises a layer comprising polyamide or ethylene vinyl alcohol.
[0112] In some embodiments, the uniaxially oriented multilayer film further comprises an outer layer that is a sealant layer.
[0113] In some embodiments, the uniaxially oriented multilayer film further comprises a layer comprising a metal deposited on an outer layer of the film, wherein the metal comprises Al, Zn, Au, Ag, Cu, Ni, Cr, Ge, Se, Ti, Sn, Si, Mg, or an oxide thereof.
[0114] In another aspect, the invention relates to an article, such as food packaging. In one aspect, an article comprises any of the inventive uniaxially oriented multilayer polyethylene films disclosed herein.
[0115] In another aspect, the invention relates to laminates and articles formed from such laminates. In some embodiments, the laminate comprises: a first film comprising a polyethylene-based sealant film, polyethylene terephthalate, polypropylene, or polyamide; and a uniaxially oriented multilayer polyethylene film according to any embodiment disclosed herein, wherein the first film is laminated to the multilayer polyethylene film. In one aspect, an article comprises any of the laminates disclosed herein.
[0116] Polyethylene composition
[0117] As discussed above, the biaxially oriented (or uniaxially oriented) multilayer film of the present invention comprises at least one layer comprising a polyethylene-based composition having certain properties. The polyethylene-based composition used in embodiments of the present invention comprises a polyethylene composition comprising: (i) 25 wt% to 37 wt% of a polyethylene having a density of 0.935 g / cm 3 Up to 0.947g / cm 3 In the range of melt index (I 2 ) less than 0.1 g / 10 minutes of the first polyethylene fraction; and (ii) 63% to 75% by weight of the second polyethylene fraction; wherein when using 13 The polyethylene composition has less than 0.10 branches per 1,000 carbon atoms when measured by C NMR, wherein the density of the polyethylene-based composition is at least 0.965 g / cm 3 , and wherein the melt index (I 2 ) is 0.5 g / 10 min to 10 g / 10 min.
[0118] In some embodiments, the melt index (I) of the polyethylene-based composition is 2 ) is 2.5 g / 10 minutes or less.
[0119] In some embodiments, the polyethylene composition comprises 25 wt % to 37 wt % of a polyethylene having a density of 0.940 g / cm 3 Up to 0.947g / cm 3 The first polyethylene fraction in the range of 63 wt % to 75 wt % has a density of 0.970 g / cm 3 or a higher second polyethylene fraction.
[0120] A polyethylene composition may comprise a combination of two or more embodiments as described herein.
[0121] In one embodiment, the polyethylene composition has a density of at least 0.965 g / cm 3 In some embodiments, the polyethylene composition has a density of at least 0.968 g / cm 3 In some embodiments, the polyethylene composition has a density of at most 0.976 g / cm 3 In some embodiments, the polyethylene composition has a weight of 0.965 g / cm 3 Up to 0.976g / cm 3 , for example 0.965 g / cm 3 Up to 0.970g / cm 3 , or 0.967 g / cm 3 Up to 0.969g / cm 3 , or 0.965 g / cm 3 Up to 0.970g / cm 3 For example, the density can be 0.965 g / cm 3 or 0.967 g / cm 3 The lower limit is 0.970g / cm 3 , 0.972g / cm 3 、0.975g / cm 3 or 0.976 g / cm 3 upper limit.
[0122] The polyethylene composition has a melt index (I) of 0.5 g / 10 min to 10 g / 10 min. 2 or I2; at 190°C / 2.16kg). For example, the melt index (I 2or I2; at 190°C / 2.16kg) can be a lower limit of 0.5g / 10min, 0.7g / 10min, 0.9g / 10min, 1.0g / 10min, 1.1g / 10min, 1.2g / 10min, 1.5g / 10min, 2g / 10min, 3g / 10min, 4g / 10min or 5g / 10min to an upper limit of 1.5g / 10min, 2g / 10min, 2.5g / 10min, 3g / 10min, 4g / 10min, 5g / 10min, 6g / 10min, 7g / 10min, 8g / 10min, 9g / 10min or 10g / 10min. In some embodiments, the polyethylene composition has a melt index (MI) of 0.5 g / 10 min to 5 g / 10 min, or 0.5 g / 10 min to 2.5 g / 10 min, or 0.7 g / 10 min to 3 g / 10 min, or 1.0 g / 10 min to 2.0 g / 10 min, or 1.0 g / 10 min to 1.5 g / 10 min. 2 ).
[0123] In some embodiments, the melt index ratio (I 10 / I 2 ) is 10 or greater. In some embodiments, the melt index ratio (I 10 / I 2 ) is at most 17. In some embodiments, the melt index ratio (I 10 / I 2 ) is 10 to 17. In some embodiments, the melt index ratio (I 10 / I 2 ) is from 12 to 17.
[0124] The polyethylene composition has a low level of branching. In some embodiments, when using 13 The polyethylene composition has less than 0.10 branches per 1,000 carbon atoms when measured by C NMR. 13 The polyethylene composition has less than 0.07 branches per 1,000 carbon atoms when measured by C NMR. 13 The polyethylene composition has less than 0.05 branches per 1,000 carbon atoms when measured by CNMR. 13 The polyethylene composition has less than 0.03 branches per 1,000 carbon atoms as measured by C NMR.
[0125] In some embodiments, the polyethylene composition has low levels of non-vinyl unsaturation. In some embodiments, when using 1The polyethylene composition has less than 25 non-vinyl unsaturations per million carbons as measured by H NMR. 1 The polyethylene composition has less than 20 non-vinyl unsaturations per million carbons as measured by H NMR.
[0126] Without wishing to be bound by theory, it is believed that the combination of low levels of branching and low levels of non-vinyl unsaturation in the polyethylene composition provides a greater amount of crystallinity in the polyethylene composition, thereby improving its barrier properties when formed into a film.
[0127] In one embodiment, the polyethylene composition has a ZSVR value of less than 2.0, or from 1.0 to 2.0, or from 1.2 to 1.8, or from 1.3 to 1.7.
[0128] In one embodiment, the molecular weight of the polyethylene composition is expressed as the ratio of weight average molecular weight to number average molecular weight (M w / M n ; as determined by conventional GPC) in the range of 8.0 to 14.0. For example, the molecular weight distribution (M w / M n ) can be a lower limit of 8.0, 8.5, 9.0 or 9.5 to an upper limit of 10.0, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5 or 14.0. In some embodiments, M w / M n It is 10.0 to 12.0.
[0129] In one embodiment, the number average molecular weight (M) of the polyethylene composition is n ; as determined by conventional GPC) in the range of 8,000 g / mol to 20,000 g / mol. For example, the number average molecular weight can be a lower limit of 8,000 g / mol, 9,000 g / mol, 10,000 g / mol, or 11,000 g / mol to an upper limit of 12,000 g / mol, 13,000 g / mol, 15,000 g / mol, or 20,000 g / mol.
[0130] In one embodiment, the weight average molecular weight (M) of the polyethylene composition is w ; as determined by conventional GPC) in the range of 100,000 g / mol to 125,000 g / mol. For example, the weight average molecular weight can be a lower limit of 100,000 g / mol, 105,000 g / mol, or 110,000 g / mol to an upper limit of 115,000 g / mol, 120,000 g / mol, or 124,000 g / mol.
[0131] In one embodiment, the z-average molecular weight (M) of the polyethylene composition is Z The z-average molecular weight (as determined by conventional GPC) is at least 350,000 g / mole, such as in the range of 350,000 g / mole to 600,000 g / mole. For example, the z-average molecular weight can be a lower limit of 350,000 g / mole, 375,000 g / mole, 400,000 g / mole, 405,000 g / mole, or 410,000 g / mole to an upper limit of 420,000 g / mole, 425,000 g / mole, 450,000 g / mole, 475,000 g / mole, 500,000 g / mole, 550,000 g / mole, or 600,000 g / mole.
[0132] In one embodiment, the M of the polyethylene composition z / M w Ratio (each as determined by conventional GPC) is greater than 3.0. In some embodiments, the M of the polyethylene composition z / M w Ratio (each as determined by conventional GPC) is greater than 3.5. z / M w It may be 3.0 to 4.0, or in some embodiments, 3.5 to 4.5, or in some embodiments, 3.5 to 4.0.
[0133] In one embodiment, the polyethylene composition has a ZSVR of less than 2.0 and M z / M w Ratio (each as determined by conventional GPC) is greater than 3.0. In another embodiment, the polyethylene composition has a ZSVR of less than 2.0 and M z / M w The ratios (each as determined by conventional GPC) were greater than 3.5.
[0134] The polyethylene composition used in the polyethylene-based composition of the present invention comprises two polyethylene fractions.
[0135] The first polyethylene fraction has a molecular weight of 0.935 g / cm 3 Up to 0.947g / cm 3 In some embodiments, the first polyethylene fraction has a density of 0.940 g / cm 3 Up to 0.947g / cm 3 The density of the first polyethylene fraction. 2 ) is less than 0.1 g / 10 min. In some embodiments, the melt index (I 2) is 0.01 g / 10 min or greater. In some embodiments, the first polyethylene fraction has a melt index of 0.05 g / 10 min to 0.1 g / 10 min. In some embodiments, when using 13 The first polyethylene fraction has less than 0.10 branches per 1,000 carbon atoms as measured by C NMR.
[0136] In some embodiments, the ethylene-based polymer has a carbon content of 0.970 g / cm 3 In some embodiments, the first polyethylene fraction has a density of 0.940 g / cm 3 Up to 0.947g / cm 3 The density of the second polyethylene fraction is 0.970 g / cm 3 In some embodiments, the melt index (I 2 ) is at least 100 g / 10 min. In some embodiments, the melt index (I 2 ) is at least 100 g / 10 min and at most 10,000 g / 10 min or more. In some embodiments, the melt index (I) of the second polyethylene fraction is at least 100 g / 10 min and at most 10,000 g / 10 min or more. 2 ) is at least 100 g / 10 min and at most 10,000 g / 10 min. In some embodiments, the second polyethylene fraction has a melt index (MI) of at least 100 g / 10 min and at most 1,000 g / 10 min. 2 ).
[0137] In some embodiments, the melt index (I) of the second polyethylene fraction is 2 ) and the melt index (I 2 ) is at least 1,000.
[0138] By the total weight of the polyethylene composition, the polyethylene composition comprises 25 wt % to 37 wt % of the first polyethylene fraction and 63 wt % to 75 wt % of the second polyethylene fraction. In some embodiments, by the total weight of the polyethylene composition, the polyethylene composition comprises 30 wt % to 37 wt % of the first polyethylene fraction and 63 wt % to 70 wt % of the second polyethylene fraction.
[0139] According to the total weight of the polyethylene-based composition, the polyethylene-based composition comprises at least 97% by weight of the polyethylene composition. In some embodiments, according to the total weight of the polyethylene-based composition, the polyethylene-based composition comprises up to 99% by weight of the polyethylene composition. In some embodiments, according to the total weight of the polyethylene-based composition, the polyethylene-based composition comprises 97% to 98% by weight of the polyethylene composition.
[0140] The following discussion focuses on the preparation of polyethylene compositions used in embodiments of the present invention.
[0141] polymerization
[0142] Any conventional polymerization process may be employed to produce the polyethylene polymer. Such conventional polymerization processes include, but are not limited to, slurry polymerization processes, solution polymerization processes using one or more conventional reactors such as loop reactors, isothermal reactors, stirred tank reactors, batch reactors, and / or any combination thereof in parallel or in series. The polyethylene component may be produced, for example, via a solution phase polymerization process using one or more loop reactors, isothermal reactors, and combinations thereof.
[0143] Typically, the solution phase polymerization process is carried out at a temperature in the range of 115°C to 250°C (e.g., 115°C to 200°C) and at a pressure in the range of 300 psi to 1,000 psi (e.g., 400 psi to 750 psi) in one or more well-mixed reactors, such as one or more isothermal loop reactors or one or more adiabatic reactors. In one embodiment, in a dual reactor, the temperature in the first reactor is in the range of 115°C to 190°C (e.g., 115°C to 175°C), and the second reactor temperature is in the range of 150°C to 250°C (e.g., 130°C to 165°C). In another embodiment, in a single reactor, the temperature in the reactor is in the range of 115°C to 250°C (e.g., 115°C to 225°C).
[0144] The residence time in the solution phase polymerization process is generally in the range of 2 minutes to 30 minutes (e.g., 10 minutes to 20 minutes). Ethylene, solvent, hydrogen, one or more catalyst systems, optionally one or more cocatalysts, and optionally one or more comonomers are continuously fed into one or more reactors. Exemplary solvents include, but are not limited to, isoparaffins. For example, such solvents can be purchased from ExxonMobil Chemical Co., Houston, Texas under the name ISOPAR E. The resulting mixture of polyethylene component and solvent is then taken out from the reactor and the polyethylene component is separated. The solvent is typically recovered via a solvent recovery unit (i.e., a heat exchanger and a steam liquid separator drum), and then recycled back into the polymerization system.
[0145] In one embodiment, polyethylene polymers can be produced via solution polymerization in a dual reactor system (e.g., a dual loop reactor system), wherein ethylene is polymerized in the presence of one or more catalyst systems. In some embodiments, only ethylene is polymerized. In addition, one or more cocatalysts may be present. In another embodiment, polyethylene compositions can be produced by solution polymerization in a single reactor system such as a single loop reactor system, wherein ethylene is polymerized in the presence of two catalyst systems. In some embodiments, only ethylene is polymerized.
[0146] Catalyst system
[0147] Specific embodiments of catalyst systems that can be used to produce polyethylene compositions described herein will now be described. It should be understood that the catalyst systems of the present disclosure can be embodied in different forms and should not be construed as being limited to the specific embodiments set forth in the present disclosure. On the contrary, embodiments are provided so that the present disclosure will be thorough and complete, and the embodiments will fully convey the scope of the subject matter to those skilled in the art.
[0148] The term "independently selected" is used herein to refer to R groups (such as R 1 , R 2 , R 3 , R 4 and R 5 ) can be the same or different (e.g., R 1 , R 2 , R 3 , R 4 and R 5 can be substituted alkyl, or R 1 and R 2 may be a substituted alkyl group and R 3 The use of the singular encompasses the use of the plural, and vice versa (e.g., a hexane solvent encompasses a plurality of hexanes). A named R group will generally have an art-recognized structure corresponding to the R group having that name. These definitions are intended to supplement and illustrate, but not to exclude, definitions known to those skilled in the art.
[0149] The term "procatalyst" refers to a compound that has catalytic activity when combined with an activator. The term "activator" refers to a compound that chemically reacts with the procatalyst in a manner that converts the procatalyst into a catalytically active catalyst. As used herein, the terms "procatalyst" and "activator" are interchangeable terms.
[0150] When used to describe certain chemical groups containing carbon atoms, the form "(C x -C y)" means that the unsubstituted form of the chemical group has from x to y carbon atoms, including x and y. For example, (C 1 -C 40 )alkyl is an alkyl group having 1 to 40 carbon atoms in its unsubstituted form. In some embodiments and general structures, certain chemical groups may be substituted with one or more substituents such as RS. The use of "(C x -C y )" The chemical group defined in brackets is R S The substitution pattern may be based on any group R S The property contains more than y carbon atoms. For example, "exactly one group R S Replaced (C 1 -C 40 ) alkyl, wherein R S Phenyl (-C 6 H 5 )" may contain from 7 to 46 carbon atoms. Thus, in general, when the parenthetical phrase "(C x -C y )" is replaced by one or more carbon-containing substituents R S When substituted, both x and y are added to the substituent R from all carbon atoms. S The combined sum of the number of carbon atoms is used to determine the minimum and maximum total number of carbon atoms in a chemical group.
[0151] The term "substituted" means that at least one hydrogen atom (-H) bonded to a carbon atom or heteroatom of a corresponding unsubstituted compound or functional group is replaced by a substituent (e.g., R S The term "fully substituted" means that each hydrogen atom (H) bonded to a carbon atom or heteroatom of the corresponding unsubstituted compound or functional group is replaced by a substituent (e.g., R S The term "polysubstituted" means that at least two but less than all hydrogen atoms bonded to carbon atoms or heteroatoms of the corresponding unsubstituted compound or functional group are replaced by substituents.
[0152] The term "-H" means a hydrogen or a hydrogen group covalently bonded to another atom. "Hydrogen" and "-H" are interchangeable and, unless expressly stated, mean the same thing.
[0153] The term “(C 1 -C 40 )hydrocarbyl" means a hydrocarbon group having 1 to 40 carbon atoms, and the term "(C 1 -C 40)alkylene group" means a hydrocarbon diradical having 1 to 40 carbon atoms, wherein each hydrocarbon group and each hydrocarbon diradical is aromatic or non-aromatic, saturated or unsaturated, straight chain or branched, cyclic (including monocyclic and polycyclic, fused and non-fused polycyclic, including bicyclic; 3 or more carbon atoms) or acyclic, and is unsubstituted or replaced by one or more R S replace.
[0154] In the present disclosure, (C 1 -C 40 ) The hydrocarbon group may be unsubstituted or substituted (C 1 -C 40 ) alkyl, (C 3 -C 40 )cycloalkyl, (C 3 -C 20 )cycloalkyl-(C 1 -C 20 ) alkylene, (C 6 -C 40 ) aryl, or (C 6 -C 20 )Aryl-(C 1 -C 20 In some embodiments, the aforementioned (C 1 -C 40 Each of the hydrocarbon groups has at most 20 carbon atoms (i.e., (C 1 -C 20 )alkyl), and in other embodiments, has up to 12 carbon atoms.
[0155] The term “(C 1 -C 40 )alkyl" and "(C 1 -C 18 ) alkyl" refers to a saturated straight or branched hydrocarbon group of 1 to 40 carbon atoms or 1 to 18 carbon atoms, respectively, which is unsubstituted or substituted by one or more RS. Unsubstituted (C 1 -C 40 Examples of alkyl groups are unsubstituted (C 1 -C 20 ) alkyl; unsubstituted (C 1 -C 10 ) alkyl; unsubstituted (C 1 -C 5 )alkyl; methyl; ethyl; 1-propyl; 2-propyl; 1-butyl; 2-butyl; 2-methylpropyl; 1,1-dimethylethyl; 1-pentyl; 1-hexyl; 1-heptyl; 1-nonyl; and 1-decyl. Substituted (C 1 -C 40 Examples of alkyl groups are substituted (C1 -C 20 ) alkyl, substituted (C 1 -C 10 ) alkyl, trifluoromethyl and [C 45 ] alkyl. The term "[C 45 ] alkyl" (with square brackets) means that there are up to 45 carbon atoms in the group (including substituents) and is, for example, replaced by one R S Replaced (C 27 -C 40 ) alkyl, which are respectively (C 1 -C 5 ) alkyl. Each (C 1 -C 5 ) The alkyl group may be methyl, trifluoromethyl, ethyl, 1-propyl, 1-methylethyl or 1,1-dimethylethyl.
[0156] The term “(C 6 -C 40 ) aryl" means an unsubstituted or substituted aryl having 6 to 40 carbon atoms (one or more R S ) substituted monocyclic, bicyclic or tricyclic aromatic hydrocarbon groups, wherein at least 6 to 14 carbon atoms are aromatic ring carbon atoms, and the monocyclic-, bicyclic or tricyclic groups contain 1, 2 or 3 rings, respectively; wherein 1 ring is aromatic, and 2 or 3 rings are independently fused or non-fused, and at least one of the 2 or 3 rings is aromatic. Unsubstituted (C 6 -C 40 ) aryl groups are exemplified by unsubstituted (C 6 -C 20 ) aryl; unsubstituted (C 6 -C 18 ) aryl; 2-(C 1 -C 5 )alkyl-phenyl; 2,4-bis(C 1 -C 5 )alkyl-phenyl; phenyl; fluorenyl; tetrahydrofluorenyl; dicyclopentadienylphenyl; hexahydrodicyclopentadienylphenyl; indenyl; dihydroindenyl; naphthyl; tetrahydronaphthyl; and phenanthrene. Substituted (C 6 -C 40 ) aryl groups are exemplified by substituted (C 1 -C 20 ) aryl; substituted (C 6 -C 18 )aryl; 2,4-bis[(C 20 )alkyl]-phenyl; polyfluorophenyl; pentafluorophenyl; and fluoren-9-on-1-yl.
[0157] The term “(C 3 -C 40) Cycloalkyl refers to a saturated cyclic hydrocarbon group of 3 to 40 carbon atoms, which is unsubstituted or substituted by one or more R S Other cycloalkyl groups (e.g., (C x -C y )cycloalkyl) is defined in a similar manner as having x to y carbon atoms and being unsubstituted or substituted by one or more R S Replaced. Unsubstituted (C 3 -C 40 Examples of cycloalkyl groups are unsubstituted (C 3 -C 20 )cycloalkyl, unsubstituted (C 3 -C 10 )cycloalkyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl and cyclodecyl. 3 -C 40 Examples of cycloalkyl groups are substituted (C 3 -C 20 )cycloalkyl, substituted (C 3 -C 10 )cycloalkyl, cyclopentanone-2-yl and 1-fluorocyclohexyl.
[0158] (C 1 -C 40 Examples of the alkylene group include unsubstituted or substituted (C 6 -C 40 ) arylene, (C 3 -C 40 )cycloalkylene and (C 1 -C 40 ) alkylene (e.g., (C 1 -C 20 In some embodiments, the two radicals are on the same carbon atom (e.g., -CH 2 -) or located on adjacent carbon atoms (i.e., 1,2-diradicals), or separated by one, two, or more than two intervening carbon atoms (e.g., 1,3-diradicals, 1,4-diradicals, etc.). Some diradicals include α,ω-diradicals. α,ω-diradicals are diradicals with the largest carbon backbone spacing between radical carbons. (C 2 -C 20 Some examples of alkylene α,ω-diyl radicals include ethane-1,2-diyl (ie, -CH 2 CH 2 -), propane-1,3-diyl (i.e., -CH 2 CH 2 CH 2 -), 2-methylpropane-1,3-diyl (i.e., -CH 2 CH(CH 3 )CH2 -). (C 6 -C 50 Some examples of arylene α,ω-diyl include phenyl-1,4-diyl, naphthalene-2,6-diyl, or naphthalene-3,7-diyl.
[0159] The term “(C 1 -C 40 ")Alkylene" means a saturated straight or branched chain diradical (i.e., the point of attachment of the radical is not on a ring atom) having 1 to 40 carbon atoms, which is unsubstituted or substituted by one or more R S Replaced. Unsubstituted (C 1 -C 50 Examples of alkylene groups are unsubstituted (C 1 -C 20 ) alkylene, including unsubstituted -CH 2 CH 2 -、-(CH 2 ) 3 -、-(CH 2 ) 4 -、-(CH 2 ) 5 -、-(CH 2 ) 6 -、-(CH 2 ) 7 -、-(CH 2 ) 8 -、-CH 2 C*HCH 3 and -(CH 2 ) 4 C*(H)(CH 3 ), wherein "C*" represents a carbon atom from which a hydrogen atom is removed to form a secondary or tertiary alkyl group. 1 Examples of the alkylene group are substituted (C 1 -C 20 )alkylene, -CF 2 -, -C(O)- and -(CH 2 ) 14 C(CH 3 ) 2 (CH 2 ) 5 - (i.e., 6,6-dimethyl-substituted n-1,20-eicosene). Since the two R S can be put together to form (C 1 -C 18 ) alkylene, thus substituted (C 1 -C 50Examples of the alkylene group also include 1,2-bis(methylene)cyclopentane, 1,2-bis(methylene)cyclohexane, 2,3-bis(methylene)-7,7-dimethyl-bicyclo[2.2.1]heptane, and 2,3-bis(methylene)bicyclo[2.2.2]octane.
[0160] The term “(C 3 -C 40 ) Cycloalkylene refers to a cycloalkylene group having 3 to 40 carbon atoms which is unsubstituted or substituted with one or more R S Substituted cyclic diradicals (ie, the radicals are on ring atoms).
[0161] The term "heteroatom" refers to an atom other than hydrogen or carbon. Examples of heteroatoms include O, S, S(O), S(O) 2 、Si(R C ) 2 , P(R P )、N(R N )、-N=C(R C ) 2 , -Ge(R C ) 2 -or-Si(R C )-, where each R C , each R N and each R P For unsubstituted (C 1 -C 18 )alkyl or -H. The term "heteroalkyl" refers to a molecule or molecular framework in which one or more carbon atoms are replaced by a heteroatom. 1 -C 40 )heteroalkyl" means a heteroalkyl group having 1 to 40 carbon atoms, and the term "(C 1 -C 40 The term "heteroalkylene" means a heteroalkyl diradical having from 1 to 40 carbon atoms, each of which has one or more heteroatoms. The radical of the heteroalkyl group is located on a carbon atom or a heteroatom, and the diradical of the heteroalkyl group can be located on: (1) one or two carbon atoms, (2) one or two heteroatoms, or (3) both carbon atoms and heteroatoms. Each (C 1 -C 50 ) heteroalkyl and (C 1 -C 50 The heteroalkylene group may be unsubstituted or substituted (with one or more RS), aromatic or non-aromatic, saturated or unsaturated, linear or branched, cyclic (including monocyclic and polycyclic, fused and non-fused polycyclic) or acyclic.
[0162] (C 1 -C 40) The heteroalkyl group may be unsubstituted or substituted (C 1 -C 40 ) heteroalkyl, (C 1 -C 40 )alkyl-O-, (C 1 -C 40 )alkyl-S-, (C 1 -C 40 )alkyl-S(O)-, (C 1 -C 40 )alkyl-S(O) 2 -、(C 1 -C 40 )alkyl-Si(R C ) 2 -、(C l -C 40 )alkyl-N(R N )-、(C l -C 40 )alkyl-P(R P )-、(C 2 -C 40 ) heterocycloalkyl, (C 2 -C 19 )heterocycloalkyl-(C 1 -C 20 ) alkylene, (C 3 -C 20 )cycloalkyl-(C 1 -C 19 ) heteroalkylene, (C 2 -C 19 )heterocycloalkyl-(C 1 -C 20 ) heteroalkylene, (C 1 -C 40 ) heteroaryl, (C 1 -C 19 )heteroaryl-(C 1 -C 20 ) alkylene, (C 6 -C 20 )Aryl-(C 1 -C 19 )heteroalkylene or (C 1 -C 19 )heteroaryl-(C 1 -C 20 ) heteroalkylene.
[0163] The term “(C 4 -C 40 ) heteroaryl refers to unsubstituted or substituted (by one or more RS The monocyclic, bicyclic or tricyclic heteroaromatic hydrocarbon group is a substituted) monocyclic, bicyclic or tricyclic heteroaromatic hydrocarbon group, and the monocyclic, bicyclic or tricyclic group contains 1, 2 or 3 rings, respectively, wherein the 2 or 3 rings are independently fused or non-fused, and at least one of the 2 or 3 rings is heteroaromatic. Other heteroaryl groups (for example, usually (C x -C y ) heteroaryl, such as (C 4 -C 12 ) heteroaryl) is defined in a similar manner as having x to y carbon atoms (e.g. 4 to 12 carbon atoms) and being unsubstituted or substituted by one or more than one R S substituted. The monocyclic heteroaromatic hydrocarbon group is a 5-membered or 6-membered ring. The 5-membered ring has 5 minus h carbon atoms, where h is the number of heteroatoms and can be 1, 2 or 3; and each heteroatom can be O, S, N or P. Examples of 5-membered heteroaromatic hydrocarbon groups are pyrrol-1-yl; piperidin-2-yl; furan-3-yl; thien-2-yl; pyrazol-1-yl; isoxazol-2-yl; isothiazol-5-yl; imidazol-2-yl; oxazol-4-yl; thiazol-2-yl; 1,2,4-triazol-1-yl; 1,3,4-oxadiazol-2-yl; 1,3,4-thiadiazol-2-yl; tetrazol-1-yl; tetrazol-2-yl; and tetrazol-5-yl. The 6-membered ring has 6 minus h carbon atoms, where h is the number of heteroatoms and can be 1 or 2, and the heteroatoms can be N or P. Examples of 6-membered ring heteroaromatic hydrocarbon groups are pyridin-2-yl; pyrimidin-2-yl; and pyrazin-2-yl. Bicyclic heteroaromatic hydrocarbon groups can be fused 5,6- or 6,6-ring systems. Examples of fused 5,6-ring system bicyclic heteroaromatic hydrocarbon groups are indol-1-yl; and benzimidazol-1-yl. Examples of fused 6,6-ring system bicyclic heteroaromatic hydrocarbon groups are quinolin-2-yl; and isoquinolin-1-yl. Bicyclic heteroaromatic hydrocarbon groups can be fused 5,6,5-ring systems; 5,6,6-ring systems; 6,5,6-ring systems; or 6,6,6-ring systems. Examples of fused 5,6,5-ring systems are 1,7-dihydropyrrolo[3,2-f]indol-1-yl. Examples of fused 5,6,6-ring systems are 1H-benzo[f]indol-1-yl. An example of a fused 6,5,6-ring system is 9H-carbazol-9-yl. An example of a fused 6,5,6-ring system is 9H-carbazol-9-yl. An example of a fused 6,6,6-ring system is acridin-9-yl.
[0164] The aforementioned heteroalkyl group may be 1 -C 50 ) carbon atoms, or less carbon atoms and one or more heteroatoms. Similarly, heteroalkylene can be a saturated straight or branched chain diradical containing 1 to 50 carbon atoms and one or more heteroatoms. The heteroatoms defined above can include Si(R C )3 , Ge(R C ) 3 、Si(R C ) 2 , Ge(R C ) 2 , P(R P ) 2 , P(R P )、N(R N ) 2 、N(R N )、N、O、OR C , S, SR C , S(O) and S(O) 2 , wherein each of heteroalkyl and heteroalkylene is unsubstituted or substituted with one or more R S replace.
[0165] Unsubstituted (C 2 -C 40 )Heterocycloalkyl is exemplified by unsubstituted (C 2 -C 20 )heterocycloalkyl, unsubstituted (C 2 -C 10 )heterocycloalkyl, aziridine-1-yl, oxetan-2-yl, tetrahydrofuran-3-yl, pyrrolidin-1-yl, tetrahydrothiophene-S,S-dioxide-2-yl, morpholin-4-yl, 1,4-dioxane-2-yl, hexahydroaziridine-4-yl, 3-oxa-cyclooctyl, 5-thioxo-cyclononyl and 2-aza-cyclodecyl.
[0166] The term "halogen atom" or "halogen" refers to a free radical of a fluorine atom (F), a chlorine atom (Cl), a bromine atom (Br), or an iodine atom (I). The term "halide ion" refers to the anionic form of the following halogen atoms: fluoride ion (F - ), chloride ion (Cl - ), bromide ion (Br - ) or iodide ion (I - ).
[0167] The term "saturated" means free of carbon-carbon double bonds, carbon-carbon triple bonds, and (in heteroatom-containing groups) carbon-nitrogen, carbon-phosphorus, and carbon-silicon double bonds. S In the case of substitution, one or more double bonds and / or triple bonds may or may not be present in the substituent R S The term "unsaturated" means containing one or more carbon-carbon double bonds, carbon-carbon triple bonds and (in heteroatom-containing groups) carbon-nitrogen, carbon-phosphorus and carbon-silicon double bonds, excluding those that may be present in the substituent R SAny such double bonds may be present in a (hetero)aromatic ring (if present).
[0168] According to some embodiments, the catalyst system for producing the polyethylene composition comprises a metal-ligand complex according to formula (I):
[0169]
[0170] In formula (I), M is a metal selected from titanium, zirconium or hafnium, the metal having a formal oxidation state of +2, +3 or 4; n is 0, 1, or 2; when n is 1, X is a monodentate ligand or a bidentate ligand; when n is 2, each X is a monodentate ligand and is the same or different; the metal-ligand complex is electrically neutral as a whole; each Z is independently selected from -O-, -S-, -N(R N )-or-P(R P )-; L is (C 1 -C 40 )alkylene or (C 1 -C 40 )heteroalkylene, wherein (C 1 -C 40 ) the alkylene group has a moiety (to which L is bonded) comprising a 1-carbon atom to a 10-carbon atom connecting main chain connecting two Z groups in formula (I), or (C 1 -C 40 ) heteroalkylene has a moiety comprising a 1-atom to 10-atom connecting backbone linking two Z groups in formula (I), wherein (C 1 -C 40 ) wherein each of the 1-atom to 10-atom connected main chain of the heteroalkylene group is independently a carbon atom or a heteroatom, wherein each heteroatom is independently O, S, S(O), S(O) 2 、Si(R C ) 2 , Ge(R C ) 2 , P(R C ) or N(R C ), where each R C Independently (C 1 -C 30 ) alkyl or (C 1 -C 30 ) heteroalkyl; R 1 and R 8 Independently selected from the group consisting of: -H, (C 1 -C 40 ) alkyl, (C 1 -C 40 ) heteroalkyl, -Si(R C )3 , -Ge(R C ) 3 、-P(R P ) 2 、-N(R N ) 2 、-OR C 、-SR C 、-NO 2 、-CN、-CF 3 , R C S(O)-、R C S(O) 2 -、(R C ) 2 C=N-、R C C(O)O-、R C OC(O)-、R C C(O)N(R N )-、(R N ) 2 NC(O)-, halogen and a group of formula (II), formula (III) or formula (IV):
[0171]
[0172] In formula (II), (III) and (IV), R 31–35 , R 41–48 or R 51–59 Each of which is independently selected from (C 1 -C 40 ) alkyl, (C 1 -C 40 ) heteroalkyl, -Si(R C ) 3 , -Ge(R C ) 3 、-P(R P ) 2 、-N(R N ) 2 、-N=CHR C 、-OR C 、-SR C 、-NO 2 、-CN、-CF 3 , R C S(O)-、R C S(O) 2 -、(R C ) 2 C=N-、R C C(O)O-、R C OC(O)-、R C C(O)N(R N)-、(R N ) 2 NC(O)-, halogen or -H, limited to R 1 or R 8 At least one of the groups is a group having formula (II), formula (III) or formula (IV).
[0173] In formula (I), R 2–4 , R 5–7 and R 9–16 Each of which is independently selected from (C 1 -C 40 ) alkyl, (C 1 -C 40 ) heteroalkyl, -Si(R C ) 3 , -Ge(R C ) 3 、-P(R P ) 2 、-N(R N ) 2 、-N=CHR C 、-OR C 、-SR C 、-NO 2 、-CN、-CF 3 , R C S(O)-、R C S(O) 2 -、(R C ) 2 C=N-、R C C(O)O-、R C OC(O)-、R C C(O)N(R N )-、(R C ) 2 NC(O)-, halogen, and -H.
[0174] In some embodiments, the polyethylene component is formed in a first reactor using a first catalyst according to formula (I) and in a second reactor using a different catalyst according to formula (I).
[0175] In an exemplary embodiment using a double loop reactor, the procatalyst used in the first loop is [[2,2"'-[[bis[1-methylethyl)germane]bis(methyleneoxy-κO)]bis[3",5,5"-tris(1,1-dimethylethyl)-5'-octyl[1,1':3',1"-terphenyl]-2'-ato-κO]](2-)]dimethylzirconium having the formula C 86 H 128 F 2 GeO4 Zr and the following structure:
[0176]
[0177] In such an embodiment, the procatalyst used in the second loop is [[2,2"'-[1,3-propanediylbis(oxy-κO)]bis[3-[2,7-bis(1,1-dimethylethyl)-9H-carbazol-9-yl]]-5'-(dimethyloctylsilyl)-3'-methyl-5-(1,1,3,3-tetramethylbutyl)[1,1]-biphenyl]-2-yl-κO]](2-)]dimethylzirconium having the formula C 107 H 154 N 2 O 4 Si 2 Zr and the following structure:
[0178]
[0179] Co-catalyst component
[0180] Catalyst systems comprising metal-ligand complexes of formula (I) may be rendered catalytically active by any technique known in the art for activating metal-based catalysts for olefin polymerization reactions. For example, a system comprising a metal-ligand complex of formula (I) may be rendered catalytically active by contacting the complex with an activating cocatalyst or by combining the complex with an activating cocatalyst. Activating cocatalysts suitable for use herein include alkylaluminums; polymeric or oligomeric aluminoxanes (also referred to as aluminoxanes); neutral Lewis acids; and non-polymeric, non-coordinating, ion-forming compounds (including the use of such compounds under oxidizing conditions). A suitable activation technique is bulk electrolysis. Combinations of one or more of the foregoing activating cocatalysts and techniques are also contemplated. The term "alkylaluminum" means a monoalkylaluminum dihydride or monoalkylaluminum dihalide, a dialkylaluminum hydride or dialkylaluminum halide, or a trialkylaluminum. Examples of polymeric or oligomeric aluminoxanes include methylaluminoxane, methylaluminoxane modified with triisobutylaluminum, and isobutylaluminoxane.
[0181] Lewis acid activators (cocatalysts) include 1 to 3 (C 1 -C 20 In one embodiment, the Group 13 metal compound is tri((C 1 -C 20 ) alkyl) substituted aluminum or tri((C 1 -C 20 In other embodiments, the Group 13 metal compound is a tri(hydrocarbyl)substituted aluminum, a tri((C 1 -C20 )alkyl)-boron compounds, tri((C 1 -C 10 )alkyl)aluminum, tri((C 6 -C 18 ) aryl) boron compounds and halogenated (including perhalogenated) derivatives thereof. In other embodiments, the Group 13 metal compound is tri(fluoro-substituted phenyl) borane, tri(pentafluorophenyl) borane. In some embodiments, the activating cocatalyst is tri((C 1 -C 20 ) alkyl borate (e.g., trityl tetrafluoroborate) or tris((C 1 -C 20 )alkyl)ammoniumtetra((C 1 -C 20 )alkyl)borane (e.g., bis(octadecyl)methylammoniumtetra(pentafluorophenyl)borane). As used herein, the term "ammonium" refers to a nitrogen cation, which is ((C 1 -C 20 )alkyl) 4 N + 、((C 1 -C 20 )alkyl) 3 N(H) + 、((C 1 -C 20 )alkyl) 2 N(H) 2 + , (C 1 -C 20 )Hydrocarbon N(H) 3 + or N(H) 4 + , where there are two or more (C 1 -C 20 ) hydrocarbon groups, they may be the same or different.
[0182] The combination of neutral Lewis acid activators (cocatalysts) comprises tri((C 1 -C 4 )alkyl)aluminum and tri((C 6 -C 18In some embodiments, the present invention provides a mixture of a neutral Lewis acid mixture with a polymeric or oligomeric aluminoxane and a single neutral Lewis acid (especially tris(pentafluorophenyl)borane) with a polymeric or oligomeric aluminoxane. The ratio of moles of (metal-ligand complex):(tris(pentafluoro-phenylborane):(aluminoxane) [e.g., (Group 4 metal-ligand complex):(tris(pentafluoro-phenylborane):(aluminoxane)] is 1:1:1 to 1:10:30, and in other embodiments is 1:1:1.5 to 1:5:10.
[0183] The metal-ligand complex catalyst system comprising formula (I) can be activated by combining with one or more cocatalysts (e.g., cation-forming cocatalysts, strong Lewis acids, or combinations thereof) to form an active catalyst composition. Suitable activating cocatalysts include polymeric or oligomeric aluminoxanes (especially methylaluminoxane) and inert, compatible, non-coordinating, ion-forming compounds. Exemplary suitable cocatalysts include, but are not limited to, modified methylaluminoxane (MMAO), bis(hydrogenated tallow alkyl)methyltetrakis(pentafluorophenyl)boric acid (1 - )amines, and combinations thereof.
[0184] In some embodiments, one or more of the aforementioned activating co-catalysts are used in combination with each other. A particularly preferred combination is three (C 1 -C 4 )alkyl)aluminum, tri((C 1 -C 4 ) hydrocarbon group) borane or ammonium borate and oligomeric or polymeric aluminoxane compounds. The ratio of the total number of moles of one or more metal-ligand complexes of formula (I) to the total number of moles of one or more activating cocatalysts in the activating cocatalyst is 1:10,000 to 100:1. In some embodiments, the ratio is at least 1:5000, in some other embodiments, at least 1:1000; and 10:1 or less, and in some other embodiments, 1:1 or less. When aluminoxane is used alone as an activating cocatalyst, preferably, the number of moles of aluminoxane employed is at least 100 times the number of moles of the metal-ligand complex of formula (I). In some other embodiments, when tris (pentafluorophenyl) borane is used alone as an activating cocatalyst, the ratio of the number of moles of tris (pentafluorophenyl) borane employed to the total number of moles of one or more metal-ligand complexes of formula (I) is 0.5:1 to 10:1, 1:1 to 6:1 or 1:1 to 5:1. The remaining activating co-catalyst is generally employed in a molar amount approximately equal to the total molar amount of the one or more metal-ligand complexes of formula (I).
[0185] Nucleating Agent
[0186] The polyethylene-based composition used in the oriented multilayer film of the present invention may also include one or more nucleating agents in an embodiment. In some embodiments, the polyethylene-based composition used in the oriented multilayer film of the present invention also includes a nucleating agent, which is 1,2-cyclohexanedicarboxylic acid calcium salt or 4-[(4-chlorobenzoyl)amino] sodium benzoate. These nucleating agents, when used in appropriate amounts and in combination with the polyethylene described herein, can provide a more uniform crystal distribution and crystal size in the polyethylene film in some embodiments, which is a more uniform melting behavior of the resulting polyethylene-based composition and the film formed by the polyethylene-based composition, and subsequently, a larger operating window is provided during the orientation of the film formed by the polyethylene-based composition, while also providing one or more other improvements (e.g., stiffness, barrier properties and / or optics) of the resulting film.
[0187] However, in some embodiments, the composition based on polyethylene is substantially free of any nucleating agent. In other words, in such embodiments, the composition based on polyethylene can provide desired properties in the oriented multilayer film of the present invention, as further described herein. As used herein, in embodiments in which the composition based on polyethylene is substantially free of any nucleating agent, the composition based on polyethylene comprises 0 to less than 19ppm of total nucleating agent. In some embodiments, the composition based on polyethylene does not contain any nucleating agent. In some embodiments, the composition based on polyethylene comprises 0 to less than 19ppm of 1,2-cyclohexanedicarboxylic acid calcium salt or 4-[(4-chlorobenzoyl)amino] sodium benzoate. In some embodiments, the composition based on polyethylene does not contain any 1,2-cyclohexanedicarboxylic acid calcium salt or 4-[(4-chlorobenzoyl)amino] sodium benzoate.
[0188] In some embodiments, the nucleating agent is 1,2-cyclohexanedicarboxylic acid calcium salt. In some embodiments, the nucleating agent is sodium 4-[(4-chlorobenzoyl)amino]benzoate. In some embodiments, the polyethylene-based composition comprises both 1,2-cyclohexanedicarboxylic acid calcium salt and sodium 4-[(4-chlorobenzoyl)amino]benzoate.
[0189] Nucleating agents such as calcium salt of 1,2-cyclohexanedicarboxylic acid or sodium 4-[(4-chlorobenzoyl)amino]benzoate are heterogeneous nucleating agents. The amount and type of heterogeneous nucleating agents are important in providing desired properties. In some embodiments, the polyethylene-based composition comprises 20ppm to 5000ppm of a heterogeneous nucleating agent in the form of calcium salt of 1,2-cyclohexanedicarboxylic acid or sodium 4-[(4-chlorobenzoyl)amino]benzoate, based on the gross weight of the polyethylene-based composition. In some embodiments, the polyethylene-based composition comprises 20ppm to 2000ppm of calcium salt of 1,2-cyclohexanedicarboxylic acid or sodium 4-[(4-chlorobenzoyl)amino]benzoate, based on the gross weight of the polyethylene-based composition. In some embodiments, the polyethylene-based composition comprises 500 ppm to 2000 ppm of 1,2-cyclohexanedicarboxylic acid calcium salt or sodium 4-[(4-chlorobenzoyl)amino]benzoate, based on the total weight of the polyethylene-based composition.
[0190] In some embodiments, heterogeneous nucleating agent can be provided together with fatty acid metal salt such as zinc stearate, zinc palmitate and mixture thereof.Based on the commercial preparation mode of zinc stearate, some zinc palmitates may also exist, because commercial stearic acid contains a large amount of palmitic acid usually.In some such embodiments, by the gross weight based on the composition of polyethylene, the composition based on polyethylene comprises at least one of zinc stearate and zinc palmitate of 45ppm to 1000ppm.In some embodiments, by the gross weight based on the composition of polyethylene, the composition based on polyethylene comprises zinc stearate and / or zinc palmitate of 50 to 700ppm.In some embodiments, by the gross weight based on the composition of polyethylene, the composition based on polyethylene comprises zinc stearate and / or zinc palmitate of 85 to 600ppm.
[0191] A non-limiting example of a calcium salt of 1,2-cyclohexanedicarboxylic acid that can be used in embodiments of the present invention is Hyperform HPN-20E from Milliken Chemical, Spartanburg, South Carolina. Hyperform HPN-20E contains 60 wt % to 70 wt % of calcium salt of 1,2-cyclohexanedicarboxylic acid and 30 wt % to 40 wt % of zinc stearate / zinc palmitate. In some embodiments, the polyethylene-based composition contains 20 ppm to 5000 ppm of Hyperform HPN-20E, based on the total weight of the polyethylene-based composition. In some embodiments, the polyethylene-based composition contains 20 ppm to 2000 ppm of Hyperform HPN-20E, based on the total weight of the polyethylene-based composition.
[0192] A non-limiting example of sodium 4-[(4-chlorobenzoyl)amino]benzoate that may be used in embodiments of the present invention is Hyperform HPN 210M from Milliken Chemical, Spartanburg, South Carolina.
[0193] In some embodiments, 1,2-cyclohexanedicarboxylic acid calcium salt or sodium 4-[(4-chlorobenzoyl)amino]benzoate (and fatty acid metal salts (e.g., zinc stearate and / or zinc palmitate), when also included) can be provided as a masterbatch by blending them with a carrier resin prior to combining them with the polyethylene compositions described herein. In some such embodiments, the carrier resin is a melt index (I 2 ) is 1 g / 10 min to 12 g / 10 min polyethylene. In some embodiments where calcium salt of 1,2-cyclohexanedicarboxylic acid and zinc stearate / zinc palmitate are provided as a masterbatch, the masterbatch comprises 2 wt % to 4 wt % of calcium salt of 1,2-cyclohexanedicarboxylic acid and zinc stearate / zinc palmitate based on the total weight of the masterbatch. In one embodiment, the carrier resin is a polyethylene having a density of 0.965 and a melt index (I) of 8 g / 10 min to 9 g / 10 min. 2 ) of a high density polyethylene homopolymer with a narrow molecular weight distribution. In some embodiments, the masterbatch may also include other additives. Depending on the total amount of additives included, the masterbatch may include 85 wt % to 98 wt % of the carrier resin by the total weight of the masterbatch.
[0194] Other nucleating agents that can be used in some embodiments of the present invention include those disclosed in U.S. Patent Publication Nos. 2015 / 0087758, 2015 / 0087759, and 2015 / 0086736, which are hereby incorporated by reference herein. In some embodiments, by the gross weight of the polyethylene-based composition, the polyethylene-based composition comprises 20ppm to 5000ppm of such nucleating agents. In some embodiments, by the gross weight of the polyethylene-based composition, the polyethylene-based composition comprises 20ppm to 2000ppm of such nucleating agents.
[0195] Silicon dioxide
[0196] In some embodiments, the polyethylene-based composition further comprises silica.It has been found that silica, when used in appropriate amounts and in combination with the polyethylene compositions described herein, can reduce dust levels in films formed from the polyethylene-based composition.
[0197] When the polyethylene-based composition is incorporated into the surface layer of the film, the amount of silica in the polyethylene-based composition is important for reducing dust levels. In some embodiments, the polyethylene-based composition comprises 75 ppm to 800 ppm of silica by the total weight of the polyethylene-based composition. In some embodiments, the polyethylene-based composition comprises 100 ppm to 500 ppm of silica by the total weight of the polyethylene-based composition.
[0198] One non-limiting example of silica that may be used in embodiments of the present invention is Sylobloc 45, commercially available from Grace Davison Company.
[0199] In some embodiments, talc can be used in addition to or as a replacement for silica.
[0200] In some embodiments, silica can be provided as a masterbatch by blending with a carrier resin, 1,2-cyclohexanedicarboxylic acid calcium salt or a similar nucleating agent and zinc stearate / zinc palmitate prior to combining with the polyethylene composition described herein. The masterbatch can be as described above for 1,2-cyclohexanedicarboxylic acid calcium salt and zinc stearate / zinc palmitate. The amount of silica in masterbatch form can be based on the target silica of the overall polyethylene-based composition.
[0201] Oriented multilayer films
[0202] The oriented (uniaxial or biaxial) polyethylene films of the present invention are multilayer films. As previously indicated, such films comprise at least one layer comprising the polyethylene-based composition described herein.
[0203] In some embodiments of the multilayer films of the present invention, the multilayer films may include the polyethylene-based composition in more than one layer as described, while in other embodiments, such polyethylene-based composition is provided in a single layer. The amount of polyethylene-based composition used in the films of the present invention may depend on many factors, including, for example, the other layers in the film, the desired properties of the film, the end-use application of the film, etc.
[0204] The number of layers in the film can depend on many factors, including, for example, the desired properties of the film, the desired thickness of the film, the content of the other layers of the film, the end-use application of the film, the equipment that can be used to make the film, etc. For example, the multilayer film can further include other layers that are typically included in multilayer films, including, for example, sealant layers, barrier layers, tie layers, structural layers, etc., depending on the application. In various embodiments, the multilayer blown or cast film can include up to 2 layers, 3 layers, 4 layers, 5 layers, 6 layers, 7 layers, 8 layers, 9 layers, 10 layers, or 11 layers.
[0205] In various embodiments, the other layers within the multilayer films of the present invention may include a polymer selected from the following: the polyethylene-based compositions described herein, LLDPE, VLDPE (very low density polyethylene), MDPE, LDPE, HDPE, HMWHDPE (high molecular weight HDPE), propylene-based polymers, polyolefin plastomers (POPs), polyolefin elastomers (POEs), olefin block copolymers (OBCs), ethylene vinyl acetate, ethylene acrylic acid, ethylene methacrylic acid, ethylene methyl acrylate, ethylene ethyl acrylate, ethylene butyl acrylate, isobutylene, maleic anhydride grafted polyolefins, ionomers of any of the foregoing, or combinations thereof.
[0206] In some embodiments, in addition to the polyethylene-based composition, the oriented multilayer polyethylene film further comprises a second polyethylene composition, wherein the second polyethylene composition exhibits at least two local peaks in the comonomer distribution measured by crystallization elution fractionation, excluding the soluble fraction, wherein one of the peaks is between 40°C and 95°C. In some embodiments, the fraction forming the peak between 40°C and 95°C accounts for up to 50% by weight of the composition as measured by crystallization elution fractionation. In some embodiments, the second polyethylene composition exhibits at least two local peaks in the comonomer distribution measured by crystallization elution fractionation, excluding the soluble fraction, wherein one of the peaks is between 40°C and 87°C. In some embodiments, the fraction forming the peak between 40°C and 87°C accounts for up to 50% by weight of the composition as measured by crystallization elution fractionation. In some embodiments, the density of the second polyethylene composition is 0.928 g / cm 3 Up to 0.940g / cm 3 Examples of polyethylene compositions that can be used as the second polyethylene composition include the linear low density polyethylene resins described in U.S. Patent No. 10,363,700, which is incorporated herein by reference, and the following commercially available resins: DOWLEX from The Dow Chemical Company TM 2750ST、ELITE TM 5940G and ELITE TM 5960G. In embodiments where the film comprises such a second composition, the amount and location (i.e., layer) of the second composition to be used can depend on a number of factors including, for example, the other layers in the film, the desired properties of the film, the end-use application of the film, etc. In some embodiments, the second composition is provided in a layer of the film having a polyethylene-based composition described herein.
[0207] It should be understood that in some embodiments, any of the layers in the film may further include one or more additives known to those skilled in the art (in addition to the additives described above for polyethylene-based compositions), such as antioxidants, UV stabilizers, heat stabilizers, slip agents, anti-blocking agents, pigments or colorants, processing aids, cross-linking catalysts, flame retardants, fillers, and blowing agents.
[0208] By being based on polyethylene, the oriented multilayer polyethylene film of the present invention according to some embodiments of the present invention can be incorporated into multilayer films and articles that mainly contain (if not substantially or completely contain) polyethylene to provide films and articles that are more easily recycled. For example, in addition to other advantages that the use of such polymers can provide, films that mainly include polyethylene also have improved recyclability. For example, in some embodiments, in addition to additives, the multilayer film is completely composed of ethylene-based polymers. By the total weight of the multilayer film, in some embodiments, the multilayer film may include 90% by weight of ethylene-based polymers, or in some embodiments, 95% by weight of ethylene-based polymers, or in some embodiments, 99% by weight of ethylene-based polymers, or in some embodiments, 99.9% by weight of ethylene-based polymers, or in some embodiments, 100% by weight of ethylene-based polymers.
[0209] Before orientation, the multilayer film can have a variety of thicknesses, depending on, for example, the number of layers, the intended use of the film, and other factors. In some embodiments, such polyethylene films have a thickness of 320 to 3200 microns (typically 640 to 1920 microns) before orientation.
[0210] Prior to orientation, the polyethylene film can be formed using techniques known to those skilled in the art based on the teachings herein. For example, the film can be prepared as a blown film (e.g., a water-quenched blown film) or a cast film. For example, in the case of a multilayer polyethylene film, for those layers that can be coextruded, the layers can be coextruded as a blown film or a cast film using techniques known to those skilled in the art based on the teachings herein.
[0211] In various embodiments, the polyethylene film can be uniaxially oriented or biaxially oriented using techniques known to those of ordinary skill in the art.
[0212] In some embodiments in which the film is biaxially oriented, the polyethylene film is biaxially oriented using a tenter frame sequential biaxial orientation method. Such techniques are generally known to those skilled in the art. In other embodiments, based on the teachings of this article, other techniques known to those skilled in the art (such as a double bubble orientation process) can be used to biaxially orient the polyethylene film. Typically, a tenter frame sequential biaxial orientation process is used, and the tenter frame is incorporated as part of a multilayer coextrusion production line. After extrusion from a flat die, the film is cooled on a cooling roller and immersed in a water bath filled with room temperature water. The cast film is then transferred to a series of rollers with different rotation speeds to achieve stretching in the longitudinal direction. There are several pairs of rollers in the MD stretching section of the production line, and the several pairs of rollers are oil-heated. Pairs of rollers are sequentially used as preheating rollers, stretching rollers, and rollers for relaxation and annealing. The temperature of each pair of rollers is controlled separately. After stretching in the longitudinal direction, the film web is transferred to a tenter frame hot air oven with a heating zone to stretch in the transverse direction. The first several zones are used for preheating, the following zones are used for stretching, and then the final zone is used for annealing.
[0213] In some embodiments, the polyethylene film can be oriented in the longitudinal direction at a stretch ratio of 2:1 to 9:1, or in the alternative at a stretch ratio of 2:1 to 6:1, or in the alternative at a stretch ratio of 4:1 to 6:1. In some embodiments, the polyethylene film can be oriented in the transverse direction at a stretch ratio of 2:1 to 11:1, or in the alternative at a stretch ratio of 2:1 to 9:1, or in the alternative at a stretch ratio of 6:1 to 9:1. In some embodiments, the polyethylene film is oriented in the longitudinal direction at a stretch ratio of 2:1 to 9:1, and in the transverse direction at a stretch ratio of 2:1 to 11:1. In some embodiments, the polyethylene film is oriented in the longitudinal direction at a stretch ratio of 2:1 to 6:1, and in the transverse direction at a stretch ratio of 2:1 to 9:1. In some embodiments, the polyethylene film is oriented in the longitudinal direction at a stretch ratio of 4:1 to 6:1, and in the transverse direction at a stretch ratio of 6:1 to 9:1.
[0214] In some embodiments, after orientation, the biaxially oriented film has a thickness of 5 microns to 50 microns. In some embodiments, the biaxially oriented film has a thickness of 15 microns to 40 microns.
[0215] In some embodiments, the biaxially oriented multilayer films of the present invention may exhibit a more desirable property including, for example, haze and 2% secant modulus in the machine and transverse directions.
[0216] The biaxially oriented multilayer films of the present invention exhibit a haze of less than 30% in some embodiments, or less than 25% in some embodiments, or less than 20% in some embodiments, or less than 15% in some embodiments, or less than 10% in some embodiments. The biaxially oriented multilayer films of the present invention exhibit a 2% secant modulus of at least 700 MPa in the longitudinal direction, or at least 800 MPa in some embodiments in the longitudinal direction. The biaxially oriented multilayer films of the present invention exhibit a 2% secant modulus of at least 900 MPa in the transverse direction, or at least 1000 MPa in some embodiments, or at least 1100 MPa in some embodiments. In some embodiments, the biaxially oriented films of the present invention exhibit a haze of less than 25%, a 2% secant modulus of at least 700 MPa in the longitudinal direction, and a 2% secant modulus of at least 1000 MPa in the transverse direction. In some embodiments, the biaxially oriented films of the present invention exhibit a haze of less than 10%, a 2% secant modulus of at least 800 MPa in the longitudinal direction, and a 2% secant modulus of at least 1100 MPa in the transverse direction.
[0217] In some embodiments, when the multilayer film is uniaxially oriented, the film is oriented only in the longitudinal direction. Based on the teachings herein, as known to those of ordinary skill in the art, various processing parameters are considered suitable for stretching in the longitudinal direction. For example, a uniaxially oriented multilayer film can be oriented in the longitudinal direction at a stretch ratio greater than 1:1 and less than 8:1, or a stretch ratio of 4:1 to 8:1.
[0218] In some embodiments, after orientation, the machine direction oriented film has a thickness of 5 microns to 50 microns. In some embodiments, the machine direction oriented film has a thickness of 15 microns to 40 microns.
[0219] In some embodiments, depending on, for example, the end-use application, the oriented polyethylene film can be corona treated, plasma treated, or printed using techniques known to those skilled in the art. In some embodiments, the oriented multilayer film can be surface coated with aluminum, silicon oxide, aluminum oxide, or other metals known to those of ordinary skill in the art based on the teachings herein.
[0220] Laminates
[0221] Embodiments of the present invention also include laminates incorporating oriented multilayer polyethylene films. In some embodiments, biaxially oriented multilayer polyethylene films according to embodiments of the present invention can be laminated to another film. In some embodiments, uniaxially oriented (e.g., longitudinally oriented) multilayer polyethylene films according to embodiments of the present invention can be laminated to another film.
[0222] Other films in such embodiments include polyethylene sealant film, polyethylene terephthalate, polypropylene or polyamide.Polyethylene sealant film can be a monolayer film or a multilayer film (for example, including a polymer based on ethylene greater than 90 % by weight, or a polymer based on ethylene greater than 95 % by weight, or a polymer based on ethylene greater than 99 % by weight) formed substantially by polyethylene, and the film can be sealed to another film, another laminate or itself when heated as a part of a laminate structure.Any polyethylene sealant film based on the teaching of this paper known to those of ordinary skill in the art can be used.When another film includes polyethylene terephthalate, polypropylene or polyamide, the whole film can be formed by polyethylene terephthalate, polypropylene or polyamide, or the film includes at least one layer comprising polyethylene terephthalate, polypropylene or polyamide.Those of ordinary skill in the art can select the film including polyethylene terephthalate, polypropylene or polyamide for such embodiments based on the teaching of this paper.
[0223] Laminates according to embodiments of the present invention can be formed based on the teachings of this article using techniques known to those of ordinary skill in the art. For example, an oriented multilayer polyethylene film can be laminated to another film using an adhesive. It is believed that various adhesive compositions are suitable for adhesives for preparing laminates. These adhesives may include polyurethanes, epoxy resins, acrylic acid, etc. In one embodiment, the laminate may include an adhesive layer comprising a polyurethane adhesive. The polyurethane adhesive may be solvent-free, water-based or solvent-based. In addition, the polyurethane adhesive may be a two-part formulation. The weight or thickness of the adhesive layer may depend on a variety of factors, including, for example, the desired thickness of the multilayer structure, the type of adhesive used, and other factors. In some embodiments, the adhesive layer is applied to up to 5.0 g / m 2 , or 1.0g / m 2 Up to 4.0g / m 2 , or 2.0g / m 2 Up to 3.0g / m 2 .
[0224] Laminates according to some embodiments of the present invention may also be formed by extrusion lamination.
[0225] Products
[0226] Embodiments of the present invention also relate to articles, such as packaging, formed from the oriented multilayer polyethylene films of the present invention (or from laminates incorporating such films) or incorporating such films. Such packaging may be formed from any film or laminate described herein.
[0227] The example of such articles can include flexible packaging, bags, stand-up bags and pre-made packaging or bags. In some embodiments, the oriented multilayer polyethylene film or laminate of the present invention can be used for food packaging. The example of the food that can be included in such packaging includes meat, cheese, cereals, nuts, juice, sauces, etc. Based on the teaching of this paper and based on the specific use of packaging (for example, the type of food, the amount of food, etc.), such packaging can be formed using technology known to those skilled in the art.
[0228] Test Method
[0229] Unless otherwise indicated herein, the following analytical methods are used to describe various aspects of the invention:
[0230] Melt index
[0231] Melt Index I 2 (or I2) and I 10 (or I10) is measured according to ASTM D-1238 (Method B) at 190°C and under loads of 2.16 kg and 10 kg, respectively. Its value is reported in g / 10 min.
[0232] density
[0233] Samples for density measurement were prepared according to ASTM D4703. Measurements were made according to ASTM D792, Method B within one hour of pressing the sample.
[0234] Conventional Gel Permeation Chromatography (Conventional GPC)
[0235] The GPC-IR high temperature chromatography system from PolymerChar (Valencia, Spain) was equipped with a precision detector (Amherst, MA), a 2-angle laser scattering detector model 2040, an IR5 infrared detector, and a 4-capillary viscometer (both from PolymerChar). Data collection was performed using the PolymerChar Instrument Control software and the data collection interface. The system was equipped with an online solvent degasser and pumping system from Agilent Technologies (Santa Clara, CA).
[0236] The injection temperature was controlled at 150°C. The columns used were three 10-micron "mixed B" columns from Polymer Laboratories (Shropshire, UK). The solvent used was 1,2,4-trichlorobenzene. The sample was prepared at a concentration of 0.1 grams of polymer in 50 milliliters of solvent. The chromatographic solvent and the sample preparation solvent each contained "200 ppm butylated hydroxytoluene (BHT)". Both solvent sources were bubbled with nitrogen. The ethylene-based polymer sample was gently stirred for three hours at 160 degrees Celsius. The injection volume was "200 microliters" and the flow rate was "1 milliliter / minute". The GPC column set was calibrated by running 21 polystyrene standards of "narrow molecular weight distribution". The molecular weight (MW) range of the standards was 580 g / mol to 8,400,000 g / mol, and the standards were included in six "cocktail" mixtures. Each standard mixture had at least ten times intervals between individual molecular weights. The standard mixture was purchased from Polymer Laboratories. Polystyrene standards were prepared as follows: 0.025 g in 50 mL solvent for molecular weights equal to or greater than 1,000,000 g / mol and 0.050 g in 50 mL solvent for molecular weights less than 1,000,000 g / mol.
[0237] Dissolve the polystyrene standards at 80°C for 30 minutes with gentle stirring. Run the narrow standard mixture first and follow the order of decreasing highest molecular weight component to minimize degradation. Convert the polystyrene standard peak molecular weight to polyethylene molecular weight using Equation 1 (as described by Williams and Ward, J. Polym. Sci., Polym. Letters, 6, 621 (1968)):
[0238] Mpolyethylene=A×(Mpolystyrene) B (Equation 1),
[0239] Where M is the molecular weight, A equals 0.4316 and B equals 1.0.
[0240] The number average molecular weight (Mn(conv gpc)), the weight average molecular weight (Mw-conv gpc) and the z average molecular weight (Mz(conv gpc)) were calculated according to the following Equations 2-4.
[0241]
[0242]
[0243]
[0244] In Equations 2 to 4, RV is the column retention volume (linear interval), collected at "1 point per second", IR is the baseline-subtracted IR detector signal from the IR5 measurement channel of the GPC instrument, in volts, and M is PE is the polyethylene equivalent MW determined by Equation 1. Data calculations were performed using "GPC One Software (Version 2.013H)" from PolymerChar.
[0245] Creep Zero Shear Viscosity Measurement Method
[0246] Zero shear viscosity was obtained by creep testing, which was performed at 190°C on an AR G2 stress-controlled rheometer (TAInstruments; New Castle, Del) using "25 mm diameter" parallel plates. The rheometer oven was set to the test temperature for at least 30 minutes before the fixture was zeroed. The compression-molded sample disc was inserted between the plates at the test temperature and allowed to reach equilibrium for five minutes. The upper plate was then lowered to 50 μm (instrument setting) above the desired test gap (1.5 mm). Any excess material was trimmed off and the upper plate was lowered to the desired gap. The measurement was performed at a flow rate of 5 L / min under a nitrogen purge. The default creep time was set to two hours. Each sample was compression-molded into a "2 mm thick × 25 mm diameter" circular plate at a pressure of 10 MPa in air at 177°C for five minutes. The sample was then removed from the press and placed on a counter to cool.
[0247] A constant low shear stress of 20 Pa was applied to all samples to ensure that the steady-state shear rate was low enough to be in the Newtonian region. For the samples in this study, the steady-state shear rate was 10 -3 s -1 Up to 10 -4 s -1 The steady state is determined by performing a linear regression on all data in the last 10% time window of the plot of "log(J(t)) versus log(t)", where J(t) is the creep compliance and t is the creep time. If the slope of the linear regression is greater than 0.97, steady state is considered to be reached and the creep test is stopped. In all cases in this study, the slope met the criterion within one hour. The steady-state shear rate is determined by the slope of the linear regression of all data points in the last 10% time window of the plot of "ε versus t", where ε is the strain. The zero shear viscosity is determined by the ratio of the applied stress to the steady-state shear rate.
[0248] To determine if the sample degraded during the creep test, a small amplitude oscillatory shear test from 0.1 rad / s to 100 rad / s was performed on the same sample before and after the creep test. The complex viscosity values of the two tests were compared. If the difference in viscosity values was greater than 5% at 0.1 rad / s, the sample was considered to have degraded during the creep test and the result was discarded.
[0249] Zero Shear Viscosity Ratio (ZSVR)
[0250] The zero shear viscosity ratio (ZSVR) is defined as the ratio of the zero shear viscosity (ZSV) of a branched polyethylene material to the ZSV of a linear polyethylene material at equivalent average molecular weight. According to the equation:
[0251] ZSVR=η 0B / η 0L =η 0B / (2.29 -15 X M 3.65 )
[0252] The ZSV value was obtained from creep testing at 190°C by the method described above. Mwt was determined using conventional gel permeation chromatography as described above. A correlation between the ZSV of linear polyethylene and its molecular weight was established based on a series of linear polyethylene reference materials. A lower ZSVR indicates a lower level of long chain branching.
[0253] use 13 C NMR branching measurements
[0254] Sample preparation
[0255] About 2.7 g of 0.025 M Cr(AcAc) was prepared by mixing it in a Norell 1001-7 10 mm NMR tube. 3 The samples were prepared by adding a 50 / 50 mixture of tetrachloroethane-d2 / o-dichlorobenzene to 0.20 g to 0.30 g of sample. Oxygen was removed by purging the tube with N2 for 1 minute. The sample was dissolved and homogenized by heating the tube and its contents to 120° C. to 140° C. using a heating block and a vortex mixer. Each sample was visually inspected to ensure homogeneity. The thoroughly mixed sample was not allowed to cool before being inserted into the heated NMR sample converter and / or NMR probe.
[0256] Data collection parameters
[0257] Data were collected using a Bruker 600MHz spectrometer equipped with a Bruker 10mm multicore high temperature CryoProbe. Data were acquired at a sample temperature of 120°C using 1280 transients per data file, a 7.8 second pulse repetition delay, a 90 degree flip angle, and reverse gated decoupling. All measurements were performed on non-spinning samples in locked mode. The sample was allowed to thermally equilibrate before data acquisition. 13 C NMR chemical shifts were internally referenced to the EEE triad at 30.0 ppm. The data were processed into spectra, the appropriate peaks were integrated (to quantify branching), and then one or more peak integration values or the total branches / 1000C were averaged. If branching was not detected, the detection limit of the spectrum was calculated using the integration of peaks such as those due to chain ends and the signal-to-noise ratio.
[0258] use 1 H NMR measurement of unsaturation
[0259] The stock solution (3.26 g) was added to 0.10 g to 0.13 g of polymer sample in a 10 mm NMR tube. The stock solution was tetrachloroethane-d 2 (TCE) and perchloroethylene (50:50, w:w) with 0.001M Cr 3+ or 100% TCE with 0.001M Cr 3+ A mixture of N 2 The solution in the tube was purged for 5 minutes to reduce the amount of oxygen. The sample was dissolved at 120°C to 140°C with periodic vortex mixing. 1 H NMR analyses were performed on a Bruker AVANCE 600 MHz spectrometer at 120 °C with a 10 mm cryoprobe.
[0260] Two experiments were performed to measure the degree of unsaturation: a control experiment and a double presaturation experiment. For the control experiment, the data were processed with an exponential window function with a 0.7 Hz line broadening. The residual from the TCE 1 The signal of H was set to 100, and the integral (I 总 ) is used as the signal of the whole polymer in the control experiment. The total carbon number NC in the polymer is calculated as follows:
[0261] NC=I 总计 / 2(Equation 1A).
[0262] For the double presaturation experiments, the data were processed with an exponential window function, with 0.7 Hz line broadening, and the baseline was corrected from about 7 ppm to 4 ppm. 1 The signal of H is set to 100, and the corresponding integral of the unsaturation (I 亚乙烯基 ,I三取代 ,I 乙烯基 and I 亚乙烯基 ) is integrated. It is well known that NMR spectroscopy can be used to determine the degree of unsaturation in polyethylene, see for example Busico, V. et al., Macromolecules, 2005, 38, 6988. The number of unsaturated units of vinylidene, trisubstituted, vinyl and vinylidene is calculated as follows:
[0263] N 亚乙烯基 =I 亚乙烯基 / 2 (Equation 2A),
[0264] N 三取代 =I 三取代 (Equation 3A),
[0265] N 乙烯基 =I 乙烯基 / 2 (Equation 4A),
[0266] N 亚乙烯基 =I 亚乙烯基 / 2 (Equation 5A).
[0267] The unsaturated units per 1,000 total carbons (i.e., all polymer carbons including the backbone and branches) are calculated as follows:
[0268] N 亚乙烯基 / 1,000C=(N 亚乙烯基 / NC)*1,000 (Equation 6A),
[0269] N 三取代 / 1,000C=(N 三取代 / NC)*1,000 (Equation 7A),
[0270] N 乙烯基 / 1,000C=(N 乙烯基 / NCH 2 )*1,000 (Equation 8A),
[0271] N 亚乙烯基 / 1,000C=(N 亚乙烯基 / NC)*1,000 (Equation 9A).
[0272] For the residual protons from TCE-d2 1H signal, the chemical shift reference was set to 6.0 ppm. The control was run with ZG pulses, NS=16, DS=2, AQ=1.82 s, D1=14 s (where D1 is the relaxation delay). The double presaturation experiment was run with a modified pulse sequence, where O1P=1.354 ppm, O2P=0.960 ppm, NS=50, AQ=1.82 s, D1=1 s (where D1 is the presaturation time), D13=13 s (where D13 is the relaxation delay).
[0273] Crystallization elution fractionation
[0274] Crystallization elution fractionation (CEF) was developed by Monrabal et al. Macromol.Symp .257,71-79 (2007) description. The instrument is equipped with an IR-4 detector (such as a detector commercially available from PolymerChar, Spain) and a 2040 dual-angle light scattering detector (such as those commercially available from Precision Detectors). The IR-4 detector is operated in a composition mode with two filters: C006 and B057. A 50 mm×4.6 mm 10 micron guard column (such as a guard column commercially available from PolymerLabs) is installed in the detector oven before the IR-4 detector. Ortho-dichlorobenzene (ODCB, 99% anhydrous grade) and 2,5-di-tert-butyl-4-methylphenol (BHT) are obtained (such as commercially available from Sigma-Aldrich). Silica gel 40 (particle size of 0.2 mm to 0.5 mm) is also obtained (such as commercially available from EMD Chemicals). The silica gel is dried in a vacuum oven at 160°C for about two hours before use. Eight hundred milligrams of BHT and five grams of silica gel were added to two liters of ODCB. The ODCB containing BHT and silica gel is now referred to as "ODCB". ODCB was dried with dry nitrogen (N 2 ) was bubbled for one hour. The CaCO 3 and Molecular sieves were used to obtain dry nitrogen. Sample preparation was performed with an automatic sampler at 4 mg / ml with shaking at 160°C for 2 hours. The injection volume was 300 μl. The temperature profile of CEF was: crystallization from 110°C to 30°C at 3°C / min; thermal equilibrium at 30°C for 5 minutes (including the elution time of the soluble fraction set to 2 minutes); and elution from 30°C to 140°C at 3°C / min. The flow rate during crystallization was 0.052 ml / min. The flow rate during elution was 0.50 ml / min. Data was collected at a rate of one data point per second.
[0275] According to US 2011 / 0015346 A1, the CEF column is filled with 125 μm ± 6% glass beads (such as those commercially available from MO-SCI Specialty Products) and 1 / 8 inch stainless steel tubing. The internal liquid volume of the CEF column is between 2.1 mL and 2.3 mL. Temperature calibration is performed by using a mixture of NIST standard reference materials linear polyethylene 1475a (1.0 mg / ml) and eicosane (2 mg / ml) in ODCB. The calibration consists of the following four steps: (1) The delay volume defined as the temperature shift between the measured eicosane peak elution temperature minus 30.00 °C was calculated; (2) Subtract the temperature offset of the elution temperature from the CEF raw temperature data. It should be noted that this temperature offset is a function of the experimental conditions, such as elution temperature, elution flow rate, etc. (3) Create a linear calibration line that converts elution temperature between 30.00°C and 140.00°C so that NIST linear polyethylene 1475a has a peak temperature at 101.00°C and eicosane has a peak temperature at 30.00°C, (4) For the soluble fraction measured isothermally at 30°C, the elution temperature was linearly extrapolated by using an elution heating rate of 3°C / min. The reported elution peak temperatures were obtained such that the observed comonomer content calibration curves were identical to those previously reported in US 8,372,931.
[0276] The linear baseline is calculated by selecting two data points: one data point before polymer elution, typically at a temperature of 26° C., and the other data point after polymer elution, typically at 118° C. For each data point, the detector signal is subtracted from the baseline prior to integration.
[0277] Haze
[0278] Haze was measured according to ASTM D1003 using a BYK Gardner haze meter.
[0279] 2% Secant modulus
[0280] Secant modulus at 2% strain was measured in accordance with ASTM D882-12 using an Instron universal tester in the machine direction (MD) and cross direction (CD) with a gauge length of 4 inches and a crosshead speed of 2 inches / minute.
[0281] Some embodiments of the present invention will now be described in detail in the following examples.
[0282] Example
[0283] Polyethylene composition 1
[0284] The following are examples of polyethylene-based compositions that can be used in embodiments of the biaxially oriented multilayer polyethylene films of the present invention as well as embodiments of the uniaxially oriented multilayer polyethylene films of the present invention. The embodiments of the polyethylene-based compositions described in the following examples utilize polyethylene composition 1 and polyethylene composition 2. Polyethylene composition 1 was prepared according to the following process and based on the reaction conditions reported in Table 1.
[0285] All raw materials (ethylene monomer) and process solvents (narrow boiling range high purity isoparaffin solvent, Isopar-E) were purified with molecular sieves before introduction into the reaction environment. Hydrogen was supplied under pressure in high purity grades without further purification. The reactor monomer feed stream was pressurized to greater than the reaction pressure via a mechanical compressor. The solvent feed was pressurized to greater than the reaction pressure via a pump. Each catalyst component was manually diluted in batches with purified solvent to the specified component concentration and pressurized to greater than the reaction pressure. All reaction feed streams were measured with mass flow meters and independently controlled with computer automated valve control systems.
[0286] The continuous solution polymerization reactor is composed of two non-adiabatic isothermal circulation loop reactors full of liquid that simulate the continuous stirred tank reactor (CSTR) with heat removal. All fresh solvents, monomers, hydrogen and catalyst component feeds of each reactor can be controlled independently. The temperature of all fresh feed streams (solvent, monomer and hydrogen) entering each reactor is controlled by making the feed stream pass through a heat exchanger. The total fresh feed to each polymerization reactor is injected into the reactor at two locations, wherein there is a roughly equal reactor volume between each injection position. The fresh feed entering the first reactor is usually controlled with half of the total fresh feed mass flow received by each injector. The fresh feed of the second reactor in series is usually controlled to keep half of the total ethylene mass flow near each injector, and because the unreacted ethylene from the first reactor enters the second reactor adjacent to the low-pressure fresh feed, the injector usually has less than half of the total fresh feed mass flow entering the second reactor.
[0287] The catalyst / cocatalyst components of each reactor are injected into the polymerization reactor through a specially designed injection plug. Each catalyst / cocatalyst component is injected into the same relative position in the reactor respectively, without contact time before the reactor. The computer controls the main catalyst component to maintain the single reactor monomer conversion rate under the specified target. The cocatalyst component is fed based on the calculated specified molar ratio with the main catalyst component.
[0288] The catalyst used in the first reactor was [[2,2"'-[[bis[1-methylethyl)germane]bis(methyleneoxy-κO)]bis[3",5,5"-tris(1,1-dimethylethyl)-5'-octyl[1,1':3',1"-terphenyl]-2'-ato-κO]](2-)]dimethylzirconium, having the chemical formula C 86 H 128 F 2 GeO 4 Zr and the following structure ("Catalyst 1"):
[0289]
[0290] The catalyst used in the second reactor was [[2,2″′-[1,3-propanediylbis(oxy-κO)]bis[3-[2,7-bis(1,1-dimethylethyl)-9H-carbazol-9-yl]]-5′-(dimethyloctylsilyl)-3′-methyl-5-(1,1,3,3-tetramethylbutyl)[1,1]-biphenyl]-2-radio-κO]](2-)]dimethylzirconium, having the chemical formula C 107 H 154 N 2 O 4 Si 2 Zr and the following structure ("Catalyst 2"):
[0291]
[0292] Immediately following each reactor feed injection location, the feed stream is mixed with the circulating polymerization reactor contents using static mixing elements. The contents of each reactor are continuously circulated through a heat exchanger which is responsible for removing most of the heat of reaction and where the temperature on the coolant side is responsible for maintaining an isothermal reaction environment at the specified reactor temperature. Circulation around each reactor loop is provided by a pump.
[0293] The effluent from the first polymerization reactor (containing solvent, monomer, hydrogen, catalyst components and molten polymer) leaves the first reactor loop and passes through a control valve (responsible for controlling the pressure of the first reactor at a specified target) and is injected into a second polymerization reactor of similar design. The final effluent from the second polymerization reactor enters a zone where it is deactivated by adding and reacting with a suitable reagent (water). At this same reactor outlet location, other additives are added for polymer stabilization. This final effluent stream passes through another set of static mixing elements to promote the deactivation of the catalyst and the dispersion of the additives.
[0294] After catalyst deactivation and addition of additives, the reactor effluent enters a devolatilization system where polymer is removed from the non-polymer stream. The separated polymer melt is granulated and collected. The non-polymer stream passes through various devices that separate most of the ethylene removed from the system. Most of the solvent is recycled back to the reactor after passing through a purification system. A small amount of solvent is removed from the process. Polyethylene composition 1 is stabilized with a small amount (ppm) of stabilizer.
[0295] The polymerization conditions of polyethylene composition 1 are shown in Table 1. As shown in Table 1, cocatalyst 1 (bis(hydrogenated tallow alkyl)methyl,tetrakis(pentafluorophenyl)borate (1-)amine) and cocatalyst 2 (modified methylaluminoxane (MMAO)) were used as cocatalysts for catalyst 1 and catalyst 2, respectively.
[0296] Polyethylene composition 2 was prepared using the same catalyst system as polyethylene composition 1 and using the same process with comparable reaction conditions.
[0297] Other properties of Polyethylene Composition 1 and Polyethylene Composition 2 were measured using the test methods described above and are reported in Table 2. The first polyethylene fraction refers to the polyethylene component from the first reactor and the second polyethylene fraction refers to the polyethylene fraction from the second reactor.
[0298] Table 1
[0299] <![CDATA[ Polyethylene composition 1 ]]> First reactor feed solvent / ethylene mass flow ratio g / g 6.3 The first reactor feed hydrogen / ethylene mass flow ratio g / g 1.5E-04 First reactor temperature ℃ 155 First reactor pressure barg 50 Ethylene conversion rate in the first reactor % 69.4 First Reactor Catalyst Type type Catalyst 1 First Reactor Co-catalyst 1 Type type Catalyst 1 First Reactor Co-catalyst 2 Type type Catalyst 2 First Reactor Cocatalyst 1 to Catalyst Molar Ratio (B to Zr Ratio) ratio 1.5 First Reactor Co-catalyst 2 to Catalyst Molar Ratio (Al to Zr Ratio) ratio 12.5 Second reactor feed solvent / ethylene mass flow ratio g / g 2.6 The second reactor feed hydrogen / ethylene mass flow ratio g / g 9.2E-04 Second reactor temperature ℃ 205 Second reactor pressure barg 50 Ethylene conversion rate in the second reactor % 91.1 Second Reactor Catalyst Type type Catalyst 2 Second Reactor Co-catalyst 1 Type type Catalyst 1 Second Reactor Co-catalyst 2 Type type Catalyst 2 The molar ratio of precatalyst 1 to catalyst in the second reactor (ratio of B to Zr) mol / mol 1.8 Second reactor precatalyst 2 to catalyst molar ratio (ratio of Al to Zr) mol / mol 22.9
[0300] Table 2
[0301]
[0302]
[0303] *The detection limit for this measurement is <3.
[0304] **Target
[0305] The density of the first polyethylene fraction of Polyethylene Composition 1, Total Polyethylene Composition 1 and Total Polyethylene Composition 2 was measured as described in the Test Methods section above. The density of the first polyethylene fraction of Polyethylene Composition 2 was the target value. The density of the second polyethylene fraction was calculated using the following blending rule:
[0306]
[0307] Other properties of Polyethylene Composition 1 and Polyethylene Composition 2 were evaluated and reported in Table 3.
[0308] Table 3
[0309]
[0310] Polyethylene composition 1 can be dry blended with Hyperform HPN-20E nucleating agent (Milliken Chemical) provided in a masterbatch to obtain different final loadings of HPN-20e nucleating agent ("HPN-20E"). An example of a masterbatch containing HPN-20E includes 3 wt% HPN-20E, 1.5 wt% silica, 0.5 wt% hydrotalcite, 5 wt% antioxidant, and 90 wt% carrier resin. The carrier resin can be a 0.965 g / cm 3 And the melt index (I 2 ) is a high density polyethylene homopolymer with a narrow molecular weight distribution of 8.0 g / 10 minutes. Hyperform HPN-20E contains about 66 wt% of 1,2-cyclohexanedicarboxylic acid calcium salt and about 34 wt% of zinc stearate / zinc palmitate. For subsequent examples, the masterbatch formed with Hyperform HPN-20E nucleating agent will be referred to as "Nucleating Agent Masterbatch 1".
[0311] The second masterbatch was also formed with Hyperform HPN-20E. The second masterbatch contained 10 wt% HPN-20E and 90 wt% XUS59910.08 (from The Dow Chemical Company) as a carrier resin. For subsequent examples, this will be referred to as "Nucleating Agent Masterbatch 2".
[0312] As discussed below, some of the films of the present invention include one or more nucleating agents, while other films do not include one or more nucleating agents.
[0313] Example 1
[0314] In these examples, a three-layer oriented polyethylene film was produced using a 3-layer 2.1 meter wide Biax pilot line. The film was produced using a 3-layer die with a die gap of 3.1 mm and cast on a cooling drum using an air knife pin. The film was stretched in the longitudinal direction at a stretch ratio of 5.75: 1 through a series of heated rollers at different speeds and then stretched in the transverse direction at a stretch ratio of 7.5: 1. Additional information about the production of these films is provided below.
[0315] A multilayer film having a width of 250 mm to 260 mm and a thickness of 0.8 mm to 1.2 mm is coextruded through a three-layer die at a processing temperature of about 225° C. to 260° C., and the film is cast onto a cooling drum, the surface temperature of which is controlled between 25° C. and 50° C. to solidify the unoriented film at a casting speed of about 4 to 6 meters per minute. The unoriented film is preheated at about 75° C. to 125° C. in the longitudinal direction during stretching, and is stretched in the longitudinal direction at a stretching ratio of about 6 times the original length at about 100° C. to 145° C. The resulting stretched sheet is annealed at about 20° C. to 110° C. to reduce heat shrinkage and obtain a uniaxially oriented film. The uniaxially oriented film is introduced into a tenter frame at a line speed of about 25 to 30 meters per minute, and preliminarily heated between about 115°C and 145°C, and stretched in the transverse direction at a temperature of about 110°C to 145°C with a stretch ratio of about 8 times the original width, and then heat-set or annealed at about 105°C to 135°C to reduce the internal stress caused by orientation, minimize the heat shrinkage of the final film, and provide a relatively thermally stable biaxially oriented film. After biaxial orientation, the thickness of the coextruded film is generally nominally 18 microns; the outer layers are each 3.5 microns. The biaxially oriented multilayer film can be wound into a roll. The longitudinal direction orientation relaxation ratio can be between 3-5%, and the transverse direction orientation relaxation ratio can be between 3% and 6%.
[0316] The film had the following structure A / B / C with the following corresponding thicknesses: 3.5 microns / 11 microns / 3.5 microns. The B layer was the core layer, and the A and C layers comprised both the skin and sub-skin layers of the 5-layer film stretch line. The final width was 1.1 m.
[0317] Table 3 shows the films 1-4 of the invention:
[0318] Table 3
[0319]
[0320] XUS59910.08 is a polyethylene with a density of 0.926 g / cm 3 And the melt index (I 2 ) is 1.7 g / 10 minutes, commercially available from The Dow Chemical Company and also as INNATE TM TF80 is commercially available from The Dow Chemical Company.
[0321] The haze, the 2% secant modulus in the longitudinal direction, and the 2% secant modulus in the transverse direction were measured, and the results are shown in Table 4.
[0322] Table 4
[0323]
[0324] As shown above, each of the films of the present invention exhibits a good balance of haze and 2% secant modulus, with Example 2 of the present invention exhibiting particularly low haze, higher 2% secant modulus in the transverse direction, and good 2% secant modulus in the longitudinal direction.
[0325] Example 2
[0326] The following are examples of oriented multilayer polyethylene films of the present invention that can be produced according to embodiments of the present invention.
[0327] In these embodiments, a three-layer oriented polyethylene film can be produced using a 3-layer 2.1 meter wide Biax test line. The film can be produced using a 3-layer die with a die gap of 3.1 mm, and the film is cast on a cooling drum using an air knife pin. The film can be stretched in the longitudinal direction at a stretch ratio of 6: 1 through a series of heated and different speed rollers, and then stretched in the transverse direction at a stretch ratio of 8: 1. Additional information about the production of these films is provided below.
[0328] A multilayer film having a width of 25 mm can be coextruded through a three-layer die at a processing temperature of about 225° C. to 260° C., and the film can be cast onto a cooling drum, the surface temperature of which can be controlled between 25° C. and 50° C. to solidify the unoriented film at a casting speed of about 4 to 6 meters per minute. The unoriented film can be preheated in the longitudinal direction at about 75° C. to 125° C. during stretching, and stretched in the longitudinal direction at a stretch ratio of about 6 times the original length at about 100° C. to 145° C. The resulting stretched sheet can be annealed at about 20° C. to 110° C. to reduce thermal shrinkage and obtain a uniaxially oriented film. The uniaxially oriented film can be introduced into a tenter frame at a line speed of about 25 to 30 meters per minute, and preliminarily heated between about 115°C and 145°C, and stretched in the transverse direction at a temperature of about 110°C to 145°C with a stretch ratio of about 8 times the original width, and then heat-set or annealed at about 105°C to 135°C to reduce the internal stress caused by orientation, minimize the heat shrinkage of the final film, and provide a relatively thermally stable biaxially oriented film. After biaxial orientation, the thickness of the coextruded film is generally nominally 18 microns; the outer layers are each 3.5 microns. The biaxially oriented multilayer film can be wound into a roll. The longitudinal direction orientation relaxation ratio can be between 3-5%, and the transverse direction orientation relaxation ratio can be between 3% and 6%.
[0329] The film had the following structure A / B / C with the following corresponding thicknesses: 3.5 microns / 11 microns / 3.5 microns. The B layer was the core layer, and the A and C layers comprised both the skin and sub-skin layers of the 5-layer film stretch line. The final width was 1.1 m.
[0330] Table 5 shows films 5-13 of the present invention:
[0331] Table 5
[0332]
[0333]
[0334] AFFINITY TM 1880 is commercially available from The Dow Chemical Company and has a density of 0.902 g / cm 3 And the melt index (I 2 ) is 1 gram / 10 minutes of polyolefin plastomer. In general, one of ordinary skill in the art can identify various anti-caking agents and slip agents that can be used in the C layer based on the teachings herein. An example of an anti-caking agent that can be used is CON-X AB 601PE commercially available from Kafrit Group. An example of a slip agent that can be used is CON-X SL 504PE commercially available from Kafrit Group.
[0335] In some embodiments, after extrusion, the film is not biaxially oriented, instead, the film can be oriented only in the longitudinal direction to provide a uniaxially oriented film. For example, the film can be oriented in the longitudinal direction using a Windmoeller & Hoelscher MDO film-forming stretching unit at the following temperatures: preheating from 75°C to 115°C (preheat 1 is 75°C, preheat 2 is 115°C); stretching at 125°C to 145°C; annealing at 105°C; cooling at 45°C to 75°C (e.g., 70°C). The stretch ratio in the longitudinal direction can be a stretch ratio of 4:1 to 20:1 (e.g., 4:1 to 16:1, or 4:1 to 12:1, or 4:1 to 10:1, or 4:1 to 9:1).
Claims
1. A biaxially oriented multilayer polyethylene film comprising: At least one layer, the at least one layer comprising: (1) A polyethylene-based composition, comprising: (a) at least 97 wt. %, based on the total weight of the polyethylene-based composition, of a polyethylene composition comprising: (i) 25% to 37% by weight of the density is 0.935 g / cm 3 Up to 0.947g / cm 3 A first polyethylene fraction having a melt index I2 less than 0.1 g / 10 minutes measured at 190° C. and under a load of 2.16 kg according to ASTM D-1238 Method B; and (ii) 63% to 75% by weight have a density of 0.970 g / cm 3 or greater and having a melt index I2 of at least 100 g / 10 min measured according to ASTM D-1238, Method B at 190° C. and under a 2.16 kg load; and When using 13 The polyethylene composition has less than 0.10 branches per 1,000 carbon atoms when measured by C NMR, wherein the density of the polyethylene-based composition is at least 0.965 g / cm 3 , and wherein the polyethylene-based composition has a melt index I2 of 0.5 g / 10 min to 10 g / 10 min, measured according to ASTM D-1238 Method B at 190° C. and under a load of 2.16 kg. 2 . The film of claim 1 , wherein the film is oriented in the longitudinal direction at a stretch ratio of 2:1 to 9:1 and in the transverse direction at a stretch ratio of 2:1 to 11:
1.
3. The film of claim 1 or claim 2, wherein the polyethylene-based composition comprises at least 99 wt% of the polyethylene composition, based on the total weight of the polyethylene-based composition, and is free of any nucleating agent.
4. The film of claim 1 or claim 2, wherein the polyethylene-based composition comprises at least 99 wt% of the polyethylene composition and the polyethylene-based composition comprises 0 to 19 ppm total nucleating agent, based on the total weight of the polyethylene-based composition.
5. The film of claim 1 or claim 2, wherein the polyethylene-based composition further comprises 20 ppm to 5000 ppm of a nucleating agent, based on the total weight of the polyethylene-based composition, wherein the nucleating agent comprises 1,2-cyclohexanedicarboxylic acid calcium salt or sodium 4-[(4-chlorobenzoyl)amino]benzoate.
6. The film of claim 1 or claim 2, further comprising a second polyethylene composition, wherein the second polyethylene composition exhibits at least two local peaks in comonomer distribution measured by crystallization elution fractionation, excluding the soluble fraction, wherein one of the peaks is between 40°C and 95°C.
7. The film of claim 6, wherein the layer comprising the polyethylene-based composition further comprises the second polyethylene composition.
8. The film according to claim 1 or claim 2, wherein the overall density is 0.931 g / cm 3 Up to 0.975g / cm 3 .
9. A uniaxially oriented multilayer polyethylene film comprising: At least one layer, the at least one layer comprising: (1) A polyethylene-based composition, comprising: (a) at least 97 wt. %, based on the total weight of the polyethylene-based composition, of a polyethylene composition comprising: (i) 25% to 37% by weight of the density is 0.935 g / cm 3 Up to 0.947g / cm 3 A first polyethylene fraction having a melt index I2 less than 0.1 g / 10 minutes measured at 190° C. and under a load of 2.16 kg according to ASTM D-1238 Method B; and (ii) 63% to 75% by weight have a density of 0.970 g / cm 3 or greater and having a melt index I2 of at least 100 g / 10 min measured according to ASTM D-1238, Method B at 190° C. and under a 2.16 kg load; and When using 13 The polyethylene composition has less than 0.10 branches per 1,000 carbon atoms when measured by C NMR, wherein the density of the polyethylene-based composition is at least 0.965 g / cm 3 , and wherein the polyethylene-based composition has a melt index I2 of 0.5 g / 10 min to 10 g / 10 min, measured according to ASTM D-1238 Method B at 190° C. and under a load of 2.16 kg.
10. The film of claim 9, wherein the film is oriented in the machine direction at a stretch ratio of 4:1 to 20:
1.
11. The film of claim 9 or claim 10, wherein the polyethylene-based composition comprises at least 99 wt% of the polyethylene composition, based on the total weight of the polyethylene-based composition, and is free of any nucleating agent.
12. The film of claim 9 or claim 10, wherein the polyethylene-based composition comprises at least 99 wt% of the polyethylene composition and the polyethylene-based composition comprises 0 to 19 ppm total nucleating agent, based on the total weight of the polyethylene-based composition.
13. The film of claim 9 or claim 10, wherein the polyethylene-based composition further comprises 20 ppm to 5000 ppm of a nucleating agent, based on the total weight of the polyethylene-based composition, wherein the nucleating agent comprises 1,2-cyclohexanedicarboxylic acid calcium salt or sodium 4-[(4-chlorobenzoyl)amino]benzoate.
14. The film of claim 9 or claim 10, further comprising a second polyethylene composition, wherein the second polyethylene composition exhibits at least two local peaks in comonomer distribution measured by crystallization elution fractionation, excluding the soluble fraction, wherein one of the peaks is between 40°C and 95°C.
15. The film of claim 14, wherein the layer comprising the polyethylene-based composition further comprises the second polyethylene composition.
16. An article comprising the film according to any one of claims 1 to 15.
17. A laminate comprising: a first film comprising a polyethylene sealant film, polyethylene terephthalate, polypropylene, or polyamide; as well as The oriented multilayer polyethylene film according to any one of claims 1 to 15, Wherein the first film is laminated to the multilayer polyethylene film.